A SnS / CoS dual-component metal sulfide-based negative electrode material and a preparation method and application thereof
Patent Information
- Application Number
- CN202611072026.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-20
AI Technical Summary
[0005]本发明的目的在于提供一种基于SnS/CoS双组分金属硫化物的负极材料及其制备方法和应用,以有助于解决或改善SnS负极材料电化学储钠性能有待改进的问题
本发明的基于SnS/CoS双组分金属硫化物的负极材料的制备方法中,通过引入CoS,使CoS与SnS双组分协同促进电荷传输,增强SnS的转换与合金化反应动力学,从而提升倍率性能。本发明的SnS/CoS具有丰富的介孔结构,一方面能缓解充放电过程中的体积膨胀;另一方面,介孔促进电解液向材料内部扩散,虽引发表面副反应导致前期容量衰减,但也有效缓冲了金属硫化物充放电循环中体积反复形变的机械应力,防止材料粉碎与结构破坏。此外,由于SnS和CoS具有不同的储钠电位,嵌脱钠反应可以分步进行,有效地避免在相同电压下产生过大的体积膨胀,这种协同作用提高了材料的储钠性能。
Smart Images

Figure CN122576086B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery anode material technology, specifically relating to an anode material based on SnS / CoS dual-component metal sulfide, its preparation method, and its application. Background Technology
[0002] Currently, researchers are dedicated to exploring suitable anode materials for sodium-ion batteries. Among numerous candidate materials, layered transition metal sulfides (Mo, Sn, W, Zr, V) have emerged as promising anode materials due to their high theoretical specific capacity. SnS, in particular, possesses a graphite-like layer structure, exhibiting higher conductivity, mechanical properties, and stability than its counterparts in metal oxides. Furthermore, the atomic layers are bound by van der Waals forces, facilitating the insertion and extraction of sodium ions. SnS also possesses a narrow band gap, resulting in high electrical conductivity. Simultaneously, SnS exhibits a conversion and alloying reaction mechanism in its sodium storage process, achieving a theoretical specific capacity of 872 mAh / g, 2.4 times that of commercially available hard carbon anodes.
[0003] However, while SnS is an excellent anode material for sodium batteries, its complex sodium conversion / desodiuming mechanism also presents certain limitations. The cumulative conversion and alloying processes result in a volume expansion of up to 343%, causing severe pulverization and agglomeration of the electrode material, which in turn leads to poor cycle performance of the battery anode. The semiconductor properties of SnS also limit the kinetic performance of the battery anode.
[0004] Therefore, there is a need to provide an improved technical solution that addresses the shortcomings of the existing technology. Summary of the Invention
[0005] The purpose of this invention is to provide a negative electrode material based on SnS / CoS dual-component metal sulfide, its preparation method and application, so as to help solve or improve the problem that the electrochemical sodium storage performance of SnS negative electrode materials needs to be improved.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a negative electrode material based on SnS / CoS dual-component metal sulfide, comprising the following steps: (1) synthesizing CoSnO(OH)6 nano cubic precursor by co-precipitation method; (2) heat treatment: placing the CoSnO(OH)6 nano cubic precursor downstream of a tube furnace and placing thiourea upstream of the tube furnace, heating and heat treatment under an argon atmosphere, and cooling to room temperature to obtain the negative electrode material based on SnS / CoS dual-component metal sulfide, denoted as SnS / CoS.
[0007] Preferably, in step (1), the molar ratio of Co in the Co source and Sn in the Sn source used to prepare the CoSnO(OH)6 nano cubic precursor is 7:3-4:6; in step (2), the temperature is raised to 550℃-650℃ for heat treatment for 3.5-4.5h; and the mass ratio of CoSnO(OH)6 nano cubic precursor to thiourea is 1:4.5-1:5.5.
[0008] Preferably, before step (2), the following steps are included: Step I: CoSn(OH)6 precursor and dopamine are dispersed in Tris buffer, sonicated, stirred, and separated into solid and liquid components. The resulting solid is washed and dried to obtain CoSn(OH)6@PDA. In step (2), CoSn(OH)6@PDA is used instead of CoSn(OH)6, and the resulting anode material based on SnS / CoS dual-component metal sulfide is denoted as SnS / CoS@NC.
[0009] Preferably, in step I, the concentration of dopamine dispersed in Tris buffer is 0.007-0.013 mol / L; the concentration of CoSn(OH)6 precursor dispersed in Tris buffer is 1 g / 200 mL; the sonication time is 5 min-15 min, and the stirring time is 22 h-26 h.
[0010] Preferably, after step I, the following steps are also included: step II: II-1, immerse the filter paper in the CoSn(OH)6@PDA dispersion and react; II-2, remove the filter paper and filter it to obtain the CoSn(OH)6@PDA-filter paper composite material; in step (2), the CoSn(OH)6@PDA-filter paper composite material is used instead of CoSn(OH)6@PDA, and the resulting negative electrode material based on SnS / CoS dual-component metal sulfide is denoted as SnS / CoS@NC-CNFs.
[0011] Preferably, in step II-1, the filter paper is aldehyde-modified filter paper and / or polyethyleneimine-modified filter paper; the reaction temperature is 65℃-75℃, and the reaction time is 3.5h-4.5h; the aldehyde-modified filter paper is prepared by a method including the following steps: immersing the filter paper in a solution containing triethoxysilylbutyraldehyde and reacting at 22℃-28℃ for 10h-14h; removing the filter paper, washing, and drying to obtain the aldehyde-modified filter paper; the polyethyleneimine-modified filter paper is prepared by a method including the following steps: immersing the filter paper in a polyethyleneimine assembly solution at 65℃-75℃ for 3.5h-4.5h, removing the filter paper, washing, and drying to obtain the polyethyleneimine-modified filter paper; the polyethyleneimine assembly solution contains polyethyleneimine and sodium chloride.
[0012] Preferably, in step II-1, the ratio of filter paper to CoSn(OH)6@PDA dispersion is 1 cm⁻¹. 2 8mL-1cm 2 12mL; where the amount of filter paper used is expressed in cm. 2 The volume of CoSn(OH)6@PDA dispersion used is in mL; the concentration of CoSn(OH)6@PDA in the CoSn(OH)6@PDA dispersion is 0.010 g / mL-0.014 g / mL; the concentration of triethoxysilylbutyraldehyde in the solution is 16 g / L-22 g / L; the volume ratio of filter paper to the solution containing triethoxysilylbutyraldehyde is 3 cm³. 2 8mL-3cm 2 12 mL; In the polyethyleneimine assembly solution, the concentration of polyethyleneimine is 1.8 g / L-2.2 g / L, and the concentration of NaCl is 0.18 mol / L-0.22 mol / L; The ratio of filter paper to polyethyleneimine assembly solution is 1 cm³. 2 8mL-1cm 2 12mL.
[0013] The present invention also provides a negative electrode material based on SnS / CoS dual-component metal sulfide, which adopts the following technical solution: a negative electrode material based on SnS / CoS dual-component metal sulfide, wherein the negative electrode material based on SnS / CoS dual-component metal sulfide is prepared by the method described above.
[0014] The present invention also provides a negative electrode, which adopts the following technical solution: a negative electrode, wherein the negative electrode adopts the negative electrode material based on SnS / CoS dual-component metal sulfide as described above.
[0015] The present invention also provides a sodium-ion battery, which adopts the following technical solution: a sodium-ion battery, wherein the sodium-ion battery uses the SnS / CoS dual-component metal sulfide-based negative electrode material as described above; or, the sodium-ion battery uses the negative electrode as described above.
[0016] Beneficial effects: In the preparation method of the SnS / CoS bicomponent metal sulfide-based anode material of the present invention, CoS is introduced to synergistically promote charge transport with the SnS bicomponent, enhance the conversion and alloying reaction kinetics of SnS, and thus improve rate performance. The SnS / CoS of the present invention has abundant mesoporous structure, which on the one hand alleviates volume expansion during charge and discharge; on the other hand, the mesopores promote the diffusion of electrolyte into the material interior. Although this triggers surface side reactions leading to early capacity decay, it also effectively buffers the mechanical stress caused by repeated volume deformation during the charge-discharge cycle of the metal sulfide, preventing material pulverization and structural damage. Furthermore, since SnS and CoS have different sodium storage potentials, the sodium intercalation / deintercalation reaction can proceed stepwise, effectively avoiding excessive volume expansion at the same voltage. This synergistic effect improves the sodium storage performance of the material.
[0017] This invention constructs a SnS / CoS@NC Janus heterostructure anode material based on a polydopamine (PDA)-derived nitrogen-doped carbon (NC) coating strategy. The precise construction of the SnS / CoS Janus heterostructure was successfully achieved through the spatial confinement effect of the PDA-derived NC layer coating. SnS and CoS exhibit a heterogeneous Janus distribution within the nanocubic particles, with a distinct phase interface. The performance improvement of SnS / CoS@NC stems from the synergistic effect of the Janus heterostructure construction and the NC layer coating: firstly, the built-in electric field generated by the SnS / CoS Janus heterojunction enables directional control of the interface charge, accelerating the sodium ion insertion / extraction kinetics; secondly, the PDA-derived NC layer effectively suppresses particle aggregation and volume expansion during cycling, while nitrogen doping introduces a large number of active sites, enhancing sodium ion adsorption and storage capacity, and constructing a continuous electron transport network and rapid ion diffusion channels, reducing charge transport impedance and balancing electronic conductivity and ion migration efficiency.
[0018] This invention employs a surface charge and functional group modification strategy to anchor SnS / CoS@NC nanoparticles onto a filter paper-derived three-dimensional carbon nanofiber network (CNFs; the filter paper is converted into CNFs after heat treatment), successfully preparing SnS / CoS@NC-CNFs. SnS / CoS@NC-CNFs completely retain the porous hierarchical structure of natural cellulose, with particles relatively uniformly distributed within the carbon network framework, exhibiting no obvious agglomeration. The two form a stable interfacial bond, laying the structural foundation for the material's excellent sodium storage performance.
[0019] The performance improvement of SnS / CoS@NC-CNFs (C) of this invention stems from the multiple synergistic effects of interfacial chemical bonding, cellulose-derived carbon framework support, and network channels: First, aldehyde groups modified on the cellulose surface form Schiff base bonds with the NC precursor PDA, enhancing the interfacial bonding between the carbon substrate and SnS / CoS@NC nanoparticles and increasing the loading capacity; Second, the cellulose-derived three-dimensional carbon nanofiber network constructs electron transport pathways and enhances charge transport rate; Third, the carbon network framework and its porous hierarchical structure provide structural support and buffer space for particle volume changes. Attached Figure Description
[0020] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Wherein: Figure 1 SEM images and elemental surface scans are shown below; (a) is the SEM image of SnS / CoS-3, (b) is a magnified view of (a), (c) is the SEM image of SnS / CoS-4, (d) is a magnified view of (c), (e) is the SEM image of SnS / CoS-5, (f) is a magnified view of (e), (g) is the SEM image of SnS / CoS-6, (h) is a magnified view of (g), (i) is the SEM image of pure SnS, (j) is a magnified view of (i), (k) is the SEM image of pure CoS, (l) is a magnified view of (k), and (m) is the elemental surface scan of SnS / CoS-5.
[0021] Figure 2 The images are TEM images, elemental surface scans, and HR-TEM images of SnS / CoS-5; where (a) is the TEM image, (b) is the elemental surface scan, and (c) is the HR-TEM image.
[0022] Figure 3 XRD spectra are shown below; (a) shows the XRD spectra of SnS / CoS-3, SnS / CoS-4, SnS / CoS-5 and SnS / CoS-6, and (b) shows the XRD spectra of pure SnS and pure CoS.
[0023] Figure 4 The following are nitrogen adsorption-desorption isotherms and pore size distribution diagrams for SnS / CoS-5; where (a) is the nitrogen adsorption-desorption isotherm and (b) is the pore size distribution diagram.
[0024] Figure 5The images are SEM images and elemental surface scans; (a)-(c) are SEM images of SnS / CoS@NC-0.007 at different magnifications, (d) is the particle size distribution of SnS / CoS@NC-0.007, (e)-(g) are SEM images of SnS / CoS@NC-0.010 at different magnifications, (h) is the particle size distribution of SnS / CoS@NC-0.010, (i)-(k) are SEM images of SnS / CoS@NC-0.013 at different magnifications, (l) is the particle size distribution of SnS / CoS@NC-0.013, and (m) is the elemental surface scan of SnS / CoS@NC-0.010.
[0025] Figure 6 The images are TEM images, HR-TEM images, elemental surface scans, and energy dispersive spectroscopy (EDS). Among them, (a) is the TEM image of SnS / CoS@NC-0.007, (b) is the TEM image of SnS / CoS@NC-0.013, (c) is the TEM image of SnS / CoS@NC-0.010, (d) is a magnified view of (c), (e) is the HR-TEM image of SnS / CoS@NC-0.010, (f) is the elemental surface scan of SnS / CoS@NC-0.010, and (g) is the EDS of SnS / CoS@NC-0.010.
[0026] Figure 7 XRD spectra of SnS / CoS@NC-0.007, SnS / CoS@NC-0.010, and SnS / CoS@NC-0.013.
[0027] Figure 8 The nitrogen adsorption-desorption isotherms and pore size distribution diagrams for SnS / CoS@NC-0.010 are shown; where (a) is the nitrogen adsorption-desorption isotherm and (b) is the pore size distribution diagram.
[0028] Figure 9 The images are SEM images and elemental surface scans; where (a)-(d) are SEM images of SnS / CoS@NC-CNFs(P) at different magnifications, (e)-(h) are SEM images of SnS / CoS@NC-CNFs(E) at different magnifications, (i)-(l) are SEM images of SnS / CoS@NC-CNFs(C) at different magnifications, and (m) is an elemental surface scan of SnS / CoS@NC-CNFs(C).
[0029] Figure 10The images are TEM images; (a)-(c) are TEM images of SnS / CoS@NC-CNFs(P) at different magnifications, (d)-(f) are TEM images of SnS / CoS@NC-CNFs(E) at different magnifications, and (g)-(i) are TEM images of SnS / CoS@NC-CNFs(C) at different magnifications.
[0030] Figure 11 XRD spectra of SnS / CoS@NC-CNFs (P), SnS / CoS@NC-CNFs (E) and SnS / CoS@NC-CNFs (C).
[0031] Figure 12 The nitrogen adsorption-desorption isotherms and pore size distribution diagrams of SnS / CoS@NC-CNFs(C) are shown; where (a) is the nitrogen adsorption-desorption isotherm and (b) is the pore size distribution diagram.
[0032] Figure 13 The FTIR spectra are shown below; (a) is the FTIR spectrum of SnS / CoS@NC-CNFs(C), and (b) is the FTIR spectrum of SnS / CoS@NC-CNFs(E).
[0033] Figure 14 The graph shows the results of the Zeta potential test.
[0034] Figure 15 The CV curves are for SnS / CoS, pure SnS, and pure CoS; where (a) is the CV curve for SnS / CoS-3, (b) is the CV curve for SnS / CoS-4, (c) is the CV curve for SnS / CoS-5, (d) is the CV curve for SnS / CoS-6, (e) is the CV curve for pure SnS, and (f) is the CV curve for pure CoS.
[0035] Figure 16 The constant current charge-discharge curves are for SnS / CoS, pure SnS, and pure CoS; where (a) is the constant current charge-discharge curve for SnS / CoS-3, (b) is the constant current charge-discharge curve for SnS / CoS-4, (c) is the constant current charge-discharge curve for SnS / CoS-5, (d) is the constant current charge-discharge curve for SnS / CoS-6, (e) is the constant current charge-discharge curve for pure SnS, and (f) is the constant current charge-discharge curve for pure CoS.
[0036] Figure 17 Cyclic performance curves of different anode materials under constant current charge-discharge at a current density of 100 mA / g (1C) are shown; among them, (a) is the cycle performance curve of SnS / CoS and the coulombic efficiency curve of SnS / CoS-5, and (b) is the cycle performance curve of pure SnS and pure CoS.
[0037] Figure 18 The figures show the rate performance curves of different anode materials; where (a) is the rate performance curve of SnS / CoS, and (b) is the rate performance curve of pure SnS and pure CoS.
[0038] Figure 19 Electrochemical impedance spectroscopy (EIS) results for SnS / CoS, pure SnS, and pure CoS are shown; where (a) is the Nyquist curve, and (b) is the real part (Z') divided by the square root of the angular frequency (ω). -0.5 (c) is the linear relationship diagram in the low frequency region, and (d) is the equivalent analog circuit diagram.
[0039] Figure 20 The CV curves for SnS / CoS@NC are shown below; (a) is the CV curve for SnS / CoS@NC-0.007, (b) is the CV curve for SnS / CoS@NC-0.010, and (c) is the CV curve for SnS / CoS@NC-0.013.
[0040] Figure 21 The constant current charge-discharge curves of SnS / CoS@NC are shown below; (a) is the constant current charge-discharge curve of SnS / CoS@NC-0.007, (b) is the constant current charge-discharge curve of SnS / CoS@NC-0.010, and (c) is the constant current charge-discharge curve of SnS / CoS@NC-0.013.
[0041] Figure 22 Figures show the test results of the cycling performance and rate performance of SnS / CoS@NC; (a) shows the cycling performance curve of SnS / CoS@NC and the coulombic efficiency curve of SnS / CoS@NC-0.010, (b) shows the comparison of discharge specific capacity of the first cycle and the 200th cycle, (c) shows the rate performance curve of SnS / CoS@NC, and (d) shows the comparison of the average discharge specific capacity at 1C rate and the return to 0.1C rate.
[0042] Figure 23 The electrochemical impedance spectroscopy (EIS) results for SnS / CoS@NC are shown; (a) is the Nyquist curve, and (b) is the square root of the real part (Z') with respect to the angular frequency (ω). -0.5 (c) is the linear relationship diagram in the low frequency region, and (d) is the equivalent analog circuit diagram.
[0043] Figure 24The images are SEM images of SnS / CoS@NC-0.010 and SnS / CoS-5 after 200 cycles at 0.1C; where (a) and (b) are SEM images of SnS / CoS@NC-0.010 after 200 cycles at different magnifications, and (c) and (d) are SEM images of SnS / CoS-5 after 200 cycles at different magnifications.
[0044] Figure 25 SEM images of different electrode sheets before and after cycling are shown below; (a) is the SEM image of SnS / CoS@NC-0.010 electrode sheet before cycling, (b) is the SEM image of SnS / CoS@NC-0.010 electrode sheet after 200 cycles, (c) is the SEM image of SnS / CoS@NC-0.007 electrode sheet before cycling, (d) is the SEM image of SnS / CoS@NC-0.007 electrode sheet after 200 cycles, (e) is the SEM image of SnS / CoS@NC-0.013 electrode sheet before cycling, (f) is the SEM image of SnS / CoS@NC-0.013 electrode sheet after 200 cycles, (g) is the SEM image of SnS / CoS-5 electrode sheet before cycling, and (h) is the SEM image of SnS / CoS-5 electrode sheet after 200 cycles.
[0045] Figure 26 The CV curves are for SnS / CoS@NC-CNFs; where (a) is the CV curve for SnS / CoS@NC-CNFs(P), (b) is the CV curve for SnS / CoS@NC-CNFs(C), and (c) is the CV curve for SnS / CoS@NC-CNFs(E).
[0046] Figure 27 The constant current charge-discharge curves of SnS / CoS@NC-CNFs are shown below; (a) is the constant current charge-discharge curve of SnS / CoS@NC-CNFs(P), (b) is the constant current charge-discharge curve of SnS / CoS@NC-CNFs(C), and (c) is the constant current charge-discharge curve of SnS / CoS@NC-CNFs(E).
[0047] Figure 28 Figures show the cycle performance and rate performance test results of SnS / CoS@NC-CNFs; (a) shows the cycle performance curve of SnS / CoS@NC-CNFs and the coulombic efficiency curve of SnS / CoS@NC-CNFs (C), (b) shows the discharge specific capacity comparison between the first cycle and the 200th cycle, (c) shows the rate performance curve of SnS / CoS@NC-CNFs, and (d) shows the average discharge specific capacity comparison between 1C rate and 0.1C rate return.
[0048] Figure 29The electrochemical impedance spectroscopy (EIS) results for SnS / CoS@NC-CNFs are shown; (a) is the Nyquist curve, and (b) is the square root of the real part (Z') with respect to the angular frequency (ω). -0.5 (c) is the linear relationship diagram in the low frequency region, and (d) is the equivalent analog circuit diagram.
[0049] Figure 30 The images are SEM images of SnS / CoS@NC-CNFs after 200 cycles at 0.1C; (a) and (b) are SEM images of SnS / CoS@NC-CNFs(P) after 200 cycles at different magnifications, (c) is SEM image of SnS / CoS@NC-CNFs(E) after 200 cycles, and (d) is SEM image of SnS / CoS@NC-CNFs(C) after 200 cycles.
[0050] Figure 31 The images show SEM images of SnS / CoS@NC-CNFs electrodes before and after cycling; (a) is the SEM image of SnS / CoS@NC-CNFs(P) electrode before cycling, (b) is the SEM image of SnS / CoS@NC-CNFs(P) electrode after 200 cycles, (c) is the SEM image of SnS / CoS@NC-CNFs(E) electrode before cycling, (d) is the SEM image of SnS / CoS@NC-CNFs(E) electrode after 200 cycles, (e) is the SEM image of SnS / CoS@NC-CNFs(C) electrode before cycling, and (f) is the SEM image of SnS / CoS@NC-CNFs(C) electrode after 200 cycles.
[0051] Figure 32 The diagram shows the crystal structure model; where (a) is pure CoS, (b) is pure SnS, and (c) is SnS / CoS.
[0052] Figure 33 The diagram shows the crystal structure model of sodium ion adsorption; where (a) is pure CoS, (b) is pure SnS, and (c) is SnS / CoS.
[0053] Figure 34 The figures show the calculated charge difference density and the built-in electric field and charge density difference distribution of the SnS / CoS heterojunction; where (a) is the charge difference density diagram of SnS / CoS, and (b) is the pure CoS adsorbed Na... + The charge difference density plots after that, (c) shows pure SnS adsorbed with Na + The charge difference density plot after that, (d) shows the SnS / CoS adsorption of Na +(e) Schematic diagram of the built-in electric field formed by the SnS / CoS heterojunction, and (f) Schematic diagram of the charge density difference distribution of the SnS / CoS heterojunction.
[0054] Figure 35 for Na + Figure showing the calculated adsorption energies on pure SnS, pure CoS, and SnS / CoS surfaces.
[0055] Figure 36 for Na + The calculated diffusion barriers for pure SnS, pure CoS, and SnS / CoS along seven diffusion sites are shown in the figure. Detailed Implementation
[0056] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.
[0057] The present invention will now be described in detail with reference to embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.
[0058] To address the issue that the electrochemical performance of SnS anode materials in existing technologies needs improvement, this invention proposes a method for preparing anode materials based on SnS / CoS dual-component metal sulfides.
[0059] The method for preparing anode materials based on SnS / CoS dual-component metal sulfides according to embodiments of the present invention includes the following steps: (1) using CoSnO(OH)6 nano cubic precursor was synthesized by coprecipitation method; (2) heat treatment: CoSnO(OH)6 nano cubic precursor was placed downstream of tube furnace and thiourea was placed upstream of tube furnace. Heat treatment was carried out under argon atmosphere and cooled to room temperature to obtain the negative electrode material based on SnS / CoS dual-component metal sulfide, denoted as SnS / CoS.
[0060] Preferably, step (1) includes: dissolving sodium citrate and cobalt source in deionized water, mixing and stirring evenly to obtain solution A; mixing tin source and deionized water evenly to obtain solution B; mixing and stirring solution A and solution B, adding NaOH solution, stirring and then separating solid and liquid, washing the obtained solid, and drying to obtain CoSnO(OH)6 nano cubic precursor.
[0061] Preferably, the cobalt source is ; Tin source is .
[0062] In a preferred embodiment of the method for preparing the SnS / CoS bicomponent metal sulfide anode material of the present invention, in step (2), the material is heated to 550℃-650℃ (e.g., 550℃, 580℃, 600℃, 620℃ or 650℃) for 3.5h-4.5h (e.g., 3.5h, 3.8h, 4h, 4.2h or 4.5h); the mass ratio of CoSnO(OH)6 nanocubic precursor to thiourea is 1:4.5-1:5.5 (e.g., 1:4.5, 1:4.7, 1:5, 1:5.3 or 1:5.5). If the heat treatment temperature is too high, it may lead to material decomposition; if the heat treatment temperature is too low, it may lead to incomplete sulfidation and crystallization. If the proportion of thiourea is too high, it may cause the enrichment of elemental sulfur in the material, thereby introducing impurities; if the proportion of thiourea is too low, it will lead to incomplete sulfidation of the material.
[0063] Preferably, the heating rate is 2.5℃ / min-3.5℃ / min (e.g., 2.5℃ / min, 2.8℃ / min, 3.0℃ / min, 3.2℃ / min or 3.5℃ / min).
[0064] Preferably, in step (1), after solution A and solution B are mixed, the molar ratio of Co and Sn in the mixed solution is 7:3-4:6 (e.g., 7:3, 6:4, 1:1 or 4:6).
[0065] Preferably, in step (1), after stirring solutions A and B at room temperature for 25-35 minutes (e.g., 25 min, 28 min, 30 min, 32 min, or 35 min), 45-55 mL (e.g., 45 mL, 48 mL, 50 mL, 52 mL, or 55 mL) of 1.8 mol / L-2.2 mol / L (e.g., 1.8 mol / L, 1.9 mol / L, 2 mol / L, 2.1 mol / L, or 2.2 mol / L) NaOH solution is added, and the mixture is stirred for 2 hours. The addition of NaOH is to introduce hydroxide ions to generate a co-precipitate of Sn and Co hydroxides, forming the CoSnO(OH)6 nanocubic precursor. The stirring time of solutions A and B at room temperature is the process of generating the CoSnO(OH)6 nanocubic precursor; if the stirring time is too long, it will lead to nanoparticle aggregation; if the stirring time is too short, a good nanocubic structure cannot be formed.
[0066] Preferably, before step (2), the following steps are included: Step I: CoSn(OH)6 precursor and DA are dispersed in Tris buffer, sonicated (to help achieve uniform dispersion of CoSn(OH)6 precursor), stirred, solid-liquid separation is performed, and the resulting solid is washed and dried to obtain CoSn(OH)6@PDA (in this step, PDA is coated on the surface of CoSn(OH)6 nano cubic precursor by in-situ chemical polymerization); in step (2), CoSn(OH)6@PDA is used instead of CoSn(OH)6, and the resulting anode material based on SnS / CoS dual-component metal sulfide is denoted as SnS / CoS@NC.
[0067] Preferably, in step I, the concentration of DA dispersed in Tris buffer (preferably with a pH of 8.5) is 0.007-0.013 mol / L; the concentration of CoSn(OH)6 precursor dispersed in Tris buffer is 1 g / 200 mL; the sonication time is 5-15 min (e.g., 5 min, 8 min, 10 min, 12 min, or 15 min), and the stirring time is 22-26 h (e.g., 22 h, 23 h, 24 h, 25 h, or 26 h). During stirring, in-situ chemical polymerization of DA and coating of the CoSn(OH)6 precursor particles occur. If the stirring time is too long, DA over-polymerization will lead to uneven surface coating; if the stirring time is too short, too little PDA will be formed, resulting in incomplete coating.
[0068] Preferably, the Tris buffer solution is prepared by a method comprising the following steps: 3.16 g of tris(hydroxymethyl)aminomethane hydrochloride is dispersed in 190 mL of deionized water and sonicated for 20 min; the pH of the Tris solution is adjusted to 8.5 by adding 1 mol / L NaOH solution, and the mixture is transferred to a volumetric flask; the beaker is rinsed 2-3 times with deionized water, and all the washings are transferred to the volumetric flask, which is then brought to a final volume of 200 mL and shaken to mix.
[0069] Preferably, step I is followed by step II: II-1, immersing the filter paper in the CoSn(OH)6@PDA dispersion and reacting; II-2, removing the filter paper and filtering to obtain the CoSn(OH)6@PDA-filter paper composite material; in step (2), the CoSn(OH)6@PDA-filter paper composite material is used instead of CoSn(OH)6@PDA, and the resulting negative electrode material based on SnS / CoS dual-component metal sulfide is denoted as SnS / CoS@NC-CNFs.
[0070] Preferably, in step II-1, the ratio of filter paper to CoSn(OH)6@PDA dispersion is 1 cm⁻¹. 2 8mL-1cm 212mL (e.g., 1cm) 2 8mL, 1cm 2 9mL, 1cm 2 10mL, 1cm 2 11mL or 1cm 2 :12mL); where the amount of filter paper used is expressed in cm 2 The amount of CoSn(OH)6@PDA dispersion used is calculated in mL.
[0071] Preferably, in step II-1, the concentration of CoSn(OH)6@PDA in the CoSn(OH)6@PDA dispersion is 0.010 g / mL to 0.014 g / mL (e.g., 0.010 g / mL, 0.011 g / mL, 0.012 g / mL, 0.013 g / mL, or 0.014 g / mL). If the concentration of the CoSn(OH)6@PDA dispersion is too high, it will lead to uneven particle dispersion or agglomeration; if the concentration of the CoSn(OH)6@PDA dispersion is too low, it will lead to insufficient loading of active particles on the filter paper.
[0072] Preferably, step II-2 further includes washing with ethanol after filtration; after washing, filtration continues until the filter paper surface is completely dry.
[0073] In a preferred embodiment of the method for preparing the SnS / CoS dual-component metal sulfide anode material of the present invention, in step II-1, the filter paper is aldehyde-modified filter paper and / or polyethyleneimine (PEI)-modified filter paper; the reaction temperature is 65℃-75℃ (e.g., 65℃, 68℃, 70℃, 72℃ or 75℃), and the reaction time is 3.5h-4.5h (e.g., 3.5h, 3.8h, 4.0h, 4.3h or 4.5h). If the reaction temperature is too high or the reaction time is too long, excessive reaction will lead to an excessive loading of CoSn(OH)6@PDA particles on the filter paper surface, filling the filter paper pores and affecting the porous network structure of the three-dimensional carbon nanofibers derived from the heat-treated filter paper, thereby affecting the electrochemical performance. If the reaction temperature is too low or the reaction time is too short, it will result in uneven loading of CoSn(OH)6@PDA particles on the filter paper surface and insufficient metal sulfide active material in the heat-treated material, thereby affecting the electrochemical performance.
[0074] Preferably, step II-2 includes: adding the CoSn(OH)6@PDA dispersion into the funnel of the filtration device, filtering out half of it, blocking the filtration port, and letting it stand. This process ensures that the filter paper remains wet, so that the CoSn(OH)6@PDA in the solution can be fully adsorbed and reacted. Afterward, the remaining CoSn(OH)6@PDA solution in the funnel is dried, anhydrous ethanol is added, and the solution is filtered. After the surface of the filter paper is completely dry, the assembly process is completed.
[0075] In a preferred embodiment of the method for preparing the SnS / CoS dual-component metal sulfide anode material of the present invention, the aldehyde-modified filter paper is prepared by a method comprising the following steps: immersing the filter paper in a solution containing triethoxysilylbutyraldehyde (e.g., toluene can be used as a solvent), reacting at 22℃-28℃ (e.g., 22℃, 24℃, 26℃ or 28℃) for 10h-14h (e.g., 10h, 11h, 12h, 13h or 14h); removing the filter paper, washing (methanol and / or ethanol can be used for washing) to remove the physically adsorbed triethoxysilylbutyraldehyde, and drying (preferably, the drying method can be vacuum drying; the drying temperature can be 60℃) to obtain the aldehyde-modified filter paper. If the reaction time is too long or the reaction temperature is too high, it will lead to excessive aldehyde modification, excessive particle loading and agglomeration, and poor dispersion of metal sulfides, thus affecting performance. If the reaction time is too short or the reaction temperature is too low, it will lead to insufficient aldehyde modification, insufficient particle loading, and less active metal sulfide substances in the final material, thus affecting performance.
[0076] In a preferred embodiment of the method for preparing the SnS / CoS dual-component metal sulfide anode material of the present invention, the polyethyleneimine-modified filter paper is prepared by a method comprising the following steps: immersing the filter paper in a PEI assembly solution; soaking at 65℃-75℃ (e.g., 65℃, 68℃, 70℃, 72℃ or 75℃) for 3.5h-4.5h (e.g., 3.5h, 3.8h, 4.0h, 4.2h or 4.5h), then removing the filter paper, washing to remove unadsorbed PEI from the surface, and drying to obtain the polyethyleneimine-modified filter paper (filter paper@PEI); the polyethyleneimine assembly solution contains polyethyleneimine and sodium chloride. If the soaking time is too long or the soaking temperature is too high, it will lead to excessive PEI modification, an excessively thick PEI modification layer, or even filling the pores of the filter paper, affecting the particle loading and the final three-dimensional porous structure derived from the filter paper, thus affecting the performance. If the soaking time is too short or the soaking temperature is too low, it will lead to insufficient PEI modification, insufficient particle loading, and fewer metal sulfide active substances in the final material, thus affecting the performance.
[0077] Preferably, the polyethyleneimine aqueous solution is slowly added dropwise to the NaCl solution (NaCl, as a strong electrolyte, helps disperse PEI), and the mixture is continuously stirred to obtain the polyethyleneimine assembly solution.
[0078] In a preferred embodiment of the preparation method of the SnS / CoS bicomponent metal sulfide anode material of the present invention, the concentration of triethoxysilylbutyraldehyde in the solution is 16 g / L-22 g / L (e.g., 16 g / L, 18 g / L, 20 g / L or 22 g / L); the ratio of filter paper to the solution containing triethoxysilylbutyraldehyde is 3 cm³. 2 8mL-3cm 2 12mL (e.g., 3cm) 2 8mL, 3cm 2 9mL, 3cm 2 10mL, 3cm 2 11mL or 3cm 2 (12mL) In the polyethyleneimine assembly solution, the concentration of polyethyleneimine is 1.8 g / L–2.2 g / L (e.g., 1.8 g / L, 1.9 g / L, 2.0 g / L, 2.1 g / L, or 2.2 g / L), and the concentration of NaCl is 0.18 mol / L–0.22 mol / L (e.g., 0.18 mol / L, 0.19 mol / L, 0.20 mol / L, 0.21 mol / L, or 0.22 mol / L); the ratio of filter paper to polyethyleneimine assembly solution is 1 cm³. 2 8mL-1cm 2 12mL (e.g., 1cm) 2 8mL, 1cm 2 9mL, 1cm 2 10mL, 1cm 2 11mL or 1cm 2 :12mL).
[0079] The present invention also provides a negative electrode material based on SnS / CoS dual-component metal sulfide, which adopts the following technical solution: the negative electrode material based on SnS / CoS dual-component metal sulfide is prepared by the method described above.
[0080] The present invention also provides a negative electrode, which adopts the following technical solution: a negative electrode, wherein the negative electrode adopts the negative electrode material based on SnS / CoS dual-component metal sulfide as described above.
[0081] The present invention also proposes a sodium-ion battery, wherein the sodium-ion battery of the present invention uses the SnS / CoS dual-component metal sulfide-based negative electrode material as described above; or, the sodium-ion battery uses the negative electrode as described above.
[0082] Example 1 The SnS / CoS dual-component metal sulfide-based anode material in this embodiment was prepared using a method comprising the following steps: (1) Synthesis of CoSnO(OH)6 nanocubic precursor by coprecipitation method: Preparation of solution A: 1.47g and 1.19g Dissolve in 100 mL of deionized water and stir for 10 min. To prepare solution B: Add 1.75 g of the solution to 50 mL of deionized water. Stir for 10 min. Mix solution A with solution B (after mixing solutions A and B, the molar ratio of Co to Sn in the solution is 5:5), stir at room temperature for 30 min, then add 50 mL of 2 mol / L NaOH solution and stir for 2 h. Finally, collect the CoSn(OH)6 nanocubic precursor by centrifugation, wash three times each with deionized water and ethanol, and finally dry in a vacuum drying oven at 60 °C for 12 h.
[0083] (2) Synthesis of SnS / CoS via inert atmosphere heat treatment: Two separate quartz crucibles were loaded with 1.00 g of thiourea and 0.20 g of CoSn(OH)6 nanocubic precursor, respectively, and placed in the upstream (thiourea) and downstream (CoSn(OH)6 nanocubic precursor) sections of a tube furnace. The furnace was then heated to 600 °C at a heating rate of 3 °C / min and maintained for 4 h under an argon atmosphere. After cooling to room temperature, the final SnS / CoS bicomponent metal sulfide-based anode material was obtained.
[0084] Among them, the solution A in step (1) is changed and in solution B The amount of Co added was determined, and the molar ratio of Co to Sn in the solution after mixing solution A and solution B was set to be 7:3, 6:4, 5:5 and 4:6, respectively. The products prepared under different molar ratios were denoted as SnS / CoS-3, SnS / CoS-4, SnS / CoS-5 and SnS / CoS-6, respectively.
[0085] Example 2 The SnS / CoS dual-component metal sulfide-based anode material in this embodiment was prepared using a method comprising the following steps: (1) Synthesis of CoSn(OH)6 nanocubic precursor by coprecipitation method: Preparation of solution A: 1.47g and 1.19g Dissolve in 100 mL of deionized water and stir for 10 min. To prepare solution B: Add 1.75 g of the solution to 50 mL of deionized water. Stir for 10 min. Mix solution A with solution B (after mixing solutions A and B, the molar ratio of Co to Sn in the solution is 5:5), stir at room temperature for 30 min, then add 50 mL of 2 mol / L NaOH solution and stir for 2 h. Finally, collect the CoSnO(OH)₅ nanocubic precursor by centrifugation, wash three times each with deionized water and ethanol, and finally dry in a vacuum drying oven at 60 °C for 12 h.
[0086] I. PDA was coated onto the surface of CoSn(OH)6 nanoparticles via in-situ chemical polymerization. 1.00 g of CoSn(OH)6 precursor and a certain mass of DA were dispersed in 200 mL of Tris buffer, sonicated for 10 min, and stirred with a magnetic stirrer for 24 h. The resulting CoSn(OH)6@PDA was collected by centrifugation, washed three times each with deionized water and ethanol, and dried in a vacuum drying oven at 60 °C for 12 h to obtain CoSn(OH)6@PDA.
[0087] The Tris buffer solution was prepared using the following steps: 3.16 g of tris(hydroxymethyl)aminomethane hydrochloride was weighed and dispersed in 190 mL of deionized water, and sonicated for 20 min. The pH of the Tris solution was adjusted to 8.5 by adding 1 mol / L NaOH solution, and the mixture was transferred to a volumetric flask. The beaker was rinsed 2-3 times with deionized water, and all the washings were transferred to the volumetric flask. The volume was then adjusted to 200 mL and vortexed to mix.
[0088] (2) Sulfidation heat treatment was performed using thiourea as the sulfur source under an argon atmosphere. Two separate quartz crucibles, each containing 1.00 g of thiourea, were placed in the upstream section of a tube furnace, and 0.20 g of CoSn(OH)6@PDA was placed in the downstream section of the tube furnace. The furnace was then heated to 600 °C at a heating rate of 3 °C / min under an argon atmosphere and maintained for 4 h. After cooling to room temperature, the SnS / CoS bicomponent metal sulfide-based anode material of this embodiment was prepared; that is, nitrogen-doped carbon (NC) coated SnS / CoS anode material (denoted as SnS / CoS@NC).
[0089] By adjusting the DA concentration in step I to 0.007 mol / L, 0.010 mol / L, and 0.013 mol / L, the prepared samples were named SnS / CoS@NC-0.007, SnS / CoS@NC-0.010, and SnS / CoS@NC-0.013, respectively.
[0090] Example 3 The SnS / CoS dual-component metal sulfide-based anode material in this embodiment was prepared using a method comprising the following steps: (1) Synthesis of CoSn(OH)6 nanocubic precursor by coprecipitation method: Preparation of solution A: 1.47g and 1.19g Dissolve in 100 mL of deionized water and stir for 10 min. To prepare solution B: Add 1.75 g of the solution to 50 mL of deionized water. Stir for 10 min. Mix solution A with solution B (after mixing solutions A and B, the molar ratio of Co to Sn in the solution is 5:5), stir at room temperature for 30 min, then add 50 mL of 2 mol / L NaOH solution and stir for 2 h. Finally, collect the CoSnO(OH)₅ nanocubic precursor by centrifugation, wash three times each with deionized water and ethanol, and finally dry in a vacuum drying oven at 60 °C for 12 h.
[0091] I. PDA was coated onto the surface of CoSn(OH)6 nanoparticles via in-situ chemical polymerization. 1.00 g of CoSn(OH)6 precursor and a certain mass of DA were dispersed in 200 mL of Tris buffer (DA concentration: 0.010 mol / L), sonicated for 10 min, and stirred with a magnetic stirrer for 24 h. The resulting CoSn(OH)6@PDA was collected by centrifugation, washed three times each with deionized water and ethanol, and dried in a vacuum drying oven at 60 °C for 12 h. The Tris buffer was prepared using the following steps: 3.16 g of tris(hydroxymethyl)aminomethane hydrochloride was weighed and dispersed in 190 mL of deionized water, and sonicated for 20 min. The pH of the Tris solution was adjusted to 8.5 by adding 1 mol / L NaOH solution, and the mixture was transferred to a volumetric flask. The beaker was rinsed 2-3 times with deionized water, and all the washings were transferred to the volumetric flask. The volume was adjusted to 200 mL, and the mixture was shaken to mix.
[0092] II. Schiff base reaction-supported nanoparticles: II-1. Weigh 0.12g of CoSn(OH)6@PDA prepared in step I and disperse it in 10mL of deionized water. Take a piece of aldehyde-modified filter paper and immerse it in the water. Soak the filter paper at 70℃ for Schiff base reaction for 4h.
[0093] II-2. Next, take out the filter paper obtained in step II-1 and place it in a vacuum filtration device. Turn on the vacuum pump to perform filtration and assemble CoSn(OH)6@PDA. The specific operation steps are as follows: Add 10 mL of CoSn(OH)6@PDA dispersion into the funnel of the vacuum filtration device, filter out half of it, block the filtration port, and let it stand for 5 minutes. During this process, ensure that the filter paper is kept wet so that CoSn(OH)6@PDA in the solution can be fully adsorbed and reacted. The remaining CoSn(OH)6@PDA solution in the funnel was dried by vacuum extraction, and 30 mL of anhydrous ethanol was quickly added. The mixture was then filtered for 15 min. Once the surface of the filter paper was completely dry, the assembly process was complete, and the CoSn(OH)6@PDA-filter paper composite material was obtained.
[0094] The aldehyde-modified filter paper was prepared using a method comprising the following steps: The pretreatment of cellulose filter paper includes the following steps: A. Cutting: Precisely cut the cellulose filter paper into 1cm×1cm square pieces; B. Washing: Place the filter paper pieces in a 50mL beaker, add 30mL of anhydrous ethanol to immerse them, and ultrasonically clean for 10min to remove surface impurities; C. Rinsing and drying: Rinse the filter paper pieces 3 times with deionized water (10mL each time) to remove residual ethanol; D. Spread them flat on a petri dish and vacuum dry at 30℃ for 2h.
[0095] Preparation of aldehyde-modified cellulose filter paper: 0.2 mL of triethoxysilylbutyraldehyde was dissolved in 10 mL of toluene. Three sheets of the pretreated cellulose filter paper were immersed in the solution and reacted at 25 °C for 12 h. After removal, the filter paper was ultrasonically cleaned several times alternately with methanol and ethanol to remove the physically adsorbed triethoxysilylbutyraldehyde. The aldehyde-modified filter paper was then vacuum-dried at 60 °C for 12 h.
[0096] (2) After the above-obtained material is cut into pieces, it is placed in a tube furnace. Two independent quartz crucibles are respectively loaded with 1.00 g of thiourea and 0.20 g of CoSn(OH)6@PDA-filter paper composite material and placed in the upstream and downstream parts of the tube furnace. Then, it is heated to 600°C at a heating rate of 3°C / min under an argon atmosphere and held for 4 h. After cooling to room temperature, the SnS / CoS bicomponent metal sulfide-based anode material of this embodiment (denoted as SnS / CoS@NC-CNFs(C)) is obtained.
[0097] Example 4 The only difference between this embodiment and Embodiment 3 is that PEI-modified filter paper is used in step II instead of the aldehyde-modified filter paper in Embodiment 3; all other aspects are consistent with Embodiment 3.
[0098] The product prepared in this embodiment is denoted as SnS / CoS@NC-CNFs(E).
[0099] The PEI-modified filter paper was prepared using the following steps: 0.35 g of NaCl was weighed into a 50 mL beaker, and 20 mL of deionized water was added. The mixture was stirred until completely dissolved. 120 μL of 50 wt% PEI aqueous solution was pipetted into the NaCl solution and stirred continuously for 15 min. The solution was then transferred to a volumetric flask, and the volume was adjusted to 30 mL with deionized water. The mixture was shaken to obtain the PEI assembly solution. A pretreated filter paper was placed in a beaker containing 10 mL of the PEI assembly solution, ensuring that the filter paper was completely submerged and free of air bubbles. After soaking at 70 °C for 4 h, the filter paper was removed with tweezers and placed in a beaker containing 0.2 mol / L NaCl washing solution. The paper was gently rinsed three times to remove any unadsorbed PEI from the surface. The paper was then vacuum-dried at 60 °C for 12 h to obtain the aldehyde-modified filter paper (cellulose filter paper@PEI).
[0100] Example 5 The only difference between this embodiment and Embodiment 3 is that in step II, cellulose filter paper (obtained through pretreatment; the pretreatment method is the same as in Embodiment 3) is used instead of the aldehyde-modified filter paper in Embodiment 3; all other aspects are consistent with Embodiment 3.
[0101] The product prepared in this embodiment is denoted as SnS / CoS@NC-CNFs(P).
[0102] Comparative Example 1 The only difference between this comparative example and Example 1 is that no cobalt source is added; all other aspects are the same as in Example 1.
[0103] The product obtained in this comparative example is pure SnS.
[0104] Comparative Example 2 The only difference between this comparative example and Example 1 is that no tin source is added; all other aspects are the same as in Example 1.
[0105] The product obtained in this comparative example is pure CoS.
[0106] Comparative Example 3 The only difference between this comparative example and Example 2 is that the DA concentration is 0.002 mol / L; all other aspects are the same as in Example 2.
[0107] The negative electrode material obtained in this comparative example is denoted as SnS / CoS@NC-0.002.
[0108] Comparative Example 4 The only difference between this comparative example and Example 2 is that the DA concentration is 0.018 mol / L; all other aspects are the same as in Example 2.
[0109] The negative electrode material obtained in this comparative example is denoted as SnS / CoS@NC-0.018.
[0110] Comparative Example 5 The only difference between this comparative example and SnS / CoS@NC-CNFs(C) in Example 3 is that: a sheet of aldehyde-modified filter paper is taken and immersed in 5 mL of CoSn(OH)6@PDA dispersion; all other aspects are consistent with SnS / CoS@NC-CNFs(C) in Example 3.
[0111] The negative electrode material obtained in this comparative example is denoted as SnS / CoS@NC-CNFs(C1).
[0112] Comparative Example 6 The only difference between this comparative example and SnS / CoS@NC-CNFs(C) in Example 3 is that: a sheet of aldehyde-modified filter paper is immersed in 15 mL of CoSn(OH)6@PDA dispersion; all other aspects are consistent with SnS / CoS@NC-CNFs(C) in Example 3.
[0113] The negative electrode material obtained in this comparative example is denoted as SnS / CoS@NC-CNFs(C2).
[0114] Experimental Example I. Electrode preparation and battery assembly: 1. Electrode sheets were prepared using a doctor blade coating method: Active material, polyvinylidene fluoride (PVDF), and acetylene black were weighed in a mass ratio of 8:1:1 and thoroughly ground for 1 hour under infrared light irradiation to ensure uniform mixing. Then, N-methylpyrrolidone (NMP) and acetone were added dropwise to the mixed powder, and stirring continued under infrared light irradiation until a honey-like slurry was formed. The uniformly mixed slurry was then evenly coated onto copper foil using a 150µm thick doctor blade and placed in a vacuum drying oven at 60℃ for 12 hours. The dried copper foil was then cut into circular electrode sheets with a diameter of 11mm using a manual slicer. The mass of the electrode sheets and the empty copper foil were weighed using an analytical balance, and the mass of the active material on the electrode sheets was calculated to be 1.5-2.0 mg.
[0115] 2. Sodium-ion battery assembly: This invention uses a 2032-type button cell casing for assembly and testing. The electrode sheet obtained above is used as the negative electrode, the metallic sodium sheet as the positive electrode, the separator is Whatman (16mm in diameter), and the electrolyte is 1 mol / L NaClO4, prepared with ethylene carbonate and propylene carbonate (volume ratio 1:1) as solvents. The water and oxygen content in the glove box must not exceed 0.1 ppm. The half-cell assembly is performed in an argon-filled glove box according to the following assembly sequence: negative electrode casing—spring sheet—gasket—sodium sheet—electrolyte (3 drops)—separator—electrolyte (3 drops)—electrode sheet—positive electrode casing. The assembled button cell is sealed in a battery sealing machine and removed from the glove box according to the procedure, and left to stand for 12 hours for electrochemical testing.
[0116] II. Material Characterization: 1. X-ray diffraction: X-ray diffraction (XRD) is a research method that analyzes the diffraction patterns of materials to obtain information such as the composition, structure, or morphology of atoms or molecules within the material. In this invention, the phase and crystal structure analyses of all synthesized materials were performed using a D8AD VANCE X-ray diffractometer manufactured by Bruker GmbH, Germany, with a Cu-K radiation source. α (λ=0.1542nm), test voltage is 40kV, test current is 40mA, scan speed is 0.2s / step, and scan range is 10°-80°.
[0117] 2. Transmission Electron Microscopy: The working principle of transmission electron microscopy (TEM) is to use a high-energy electron beam to penetrate the sample and image and analyze it through an electromagnetic lens. The equipment used in this invention is a JEOL JEM 2010 transmission electron microscope from Japan to characterize the microstructure and structure of the synthesized material. The test voltage is 200kV. Before testing, the material needs to be prepared as follows: Take an appropriate amount of the ground material and place it in a centrifuge tube. Add anhydrous ethanol and sonicate for 50 minutes to ensure the sample is uniformly dispersed in the anhydrous ethanol. Then, use a pipette to aspirate an appropriate amount of the suspension from the top of the centrifuge tube and add it to the microgrid. Finally, dry at 80°C for 2 hours.
[0118] 3. Scanning Electron Microscopy (SEM): A scanning electron microscope (SEM) is a key instrument for observing the microstructure of material surfaces. It utilizes a high-energy electron beam to scan the material surface and generates high-resolution images by collecting various signals. The materials synthesized in this invention were all analyzed for morphology using a Hitachi SU8010 cold field scanning electron microscope (Japan). Before testing, gold sputtering was performed to enhance conductivity. The samples were then placed in a vacuum chamber, and a voltage of 15 kV was selected for testing.
[0119] 4. Specific Surface Area Analysis: Among the methods for measuring the specific surface area (BET) of solid materials, gas adsorption is the most commonly used method, especially nitrogen adsorption. At low temperatures (such as liquid nitrogen temperature), a certain amount of nitrogen gas is introduced into the sample tube, and the amount of nitrogen adsorbed on the sample surface is measured. Finally, the specific surface area of the material is calculated based on BET theory. This invention uses the BELSORP Maxll specific surface area analyzer from the Japanese company, Machikebaier.
[0120] 5. Fourier Transform Infrared Spectroscopy: Fourier transform infrared spectroscopy (FTIR) can reveal the molecular structure information of materials. In this invention, the Thermo Fisher IS50 ATR-FTIR infrared spectrometer was used to characterize the functional group structure of the samples, with a wavenumber range of 4000 cm⁻¹. -1 -400cm -1 .
[0121] 6. Zeta Potential Measurement: Zeta potential measurement can be used to evaluate the surface electrical properties and stability of materials, and is an important tool for studying interfacial reaction processes. In this invention, an Austrian-Anton Paar-SurPASS 3 instrument was used, and the test was conducted at pH 8.5.
[0122] Test results: 1. Test results of Example 1 and Comparative Examples 1-2: Figure 1 These are SEM images and elemental surface scans; where (a) is the SEM image of SnS / CoS-3, (b) is a magnified view of (a), (c) is the SEM image of SnS / CoS-4, (d) is a magnified view of (c), (e) is the SEM image of SnS / CoS-5, (f) is a magnified view of (e), (g) is the SEM image of SnS / CoS-6, (h) is a magnified view of (g), (i) is the SEM image of pure SnS, (j) is a magnified view of (i), (k) is the SEM image of pure CoS, (l) is a magnified view of (k), and (m) is an elemental surface scan of SnS / CoS-5. Figure 1 As shown in (a)-(d), the particle size of SnS / CoS-3 and SnS / CoS-4 is approximately 1-3 μm, with some gaps between the particles, and the overall morphology is relatively regular. Figure 1 As seen in (e)-(f), the SnS / CoS-5 nanoparticles exhibit a reduced size and form an irregular polygonal structure, which may contribute to increasing sodium storage active sites and buffering volume change stress. Figure 1 In (g)-(h), the microstructure of SnS / CoS-6 can be observed to transform into a spherical shape and exhibit aggregation. Figure 1Images (i)-(j) and (k)-(l) are SEM images of pure SnS and pure CoS, respectively. They show severe aggregation of irregularly structured particles, forming micron-sized clumps that partially block the pore structure. Furthermore, the elemental surface scans of SnS / CoS-5 are shown below. Figure 1 As shown in (m), Sn, Co, and S are uniformly distributed in the particles without obvious local aggregation, indicating that the Co and Sn precursors are fully mixed and transformed into a uniformly distributed binary metal sulfide through a sulfidation process. The SnS and CoS binary components achieve good dispersion and composite at the nanoscale, providing a structural basis for synergistic sodium storage.
[0123] TEM was used to characterize the detailed information on the microstructure and internal structure of SnS / CoS-5. Figure 2 The images show the TEM image, elemental surface scan, and HR-TEM image of SnS / CoS-5; where (a) is the TEM image, (b) is the elemental surface scan, and (c) is the HR-TEM image. Figure 2 (a) It can be clearly observed that SnS / CoS-5 exhibits an irregular blocky morphology, with particles composed of stacked short rods, which is consistent with the micron-scale cluster structure formed by nanoparticle aggregation observed in SEM. Figure 2 In (b), it is clear that Sn, Co, and S are uniformly distributed within the irregular nanoparticles. Figure 2 In (c), it can be observed that various lattice fringes are present, and the lattice fringes with a measured interplanar spacing of 0.404 nm match well with the (110) crystal plane of the orthorhombic SnS system. The lattice fringes with interplanar spacings of 1.412 nm and 0.292 nm correspond to the (112) and (100) crystal planes of the cubic CoS crystal system, respectively. This initially indicates the successful synthesis of a SnS / CoS binary metal sulfide.
[0124] The crystal structure and its properties were elucidated through XRD pattern analysis. Figure 3 XRD spectra are shown below; (a) shows the XRD spectra of SnS / CoS-3, SnS / CoS-4, SnS / CoS-5 and SnS / CoS-6, and (b) shows the XRD spectra of pure SnS and pure CoS.
[0125] Among them, the diffraction peaks at 2θ = 21.90°, 26.02°, 27.50°, 32.01°, 39.05°, and 45.50° correspond to the (110), (120), (021), (040), (131), and (150) crystal planes of the orthorhombic SnS (JCPDS No. 14-0620); the characteristic peaks at 2θ = 30.54°, 35.26°, 46.80°, and 54.28° correspond to the (100), (101), (102), and (110) crystal planes of the cubic CoS (JCPDS No. 14-0620). This confirms the successful preparation of a SnS / CoS bicomponent metal sulfide anode material via co-precipitation. Figure 3 As can be seen in (a), as the molar ratio of Co to Sn decreases, the intensity of the corresponding CoS characteristic peak gradually weakens, while the intensity of the SnS characteristic peak gradually increases. It can be observed that the diffraction peaks of SnS / CoS-5 (Co:Sn=5:5) are sharp and have good crystallinity; this microstructure feature of uniform distribution of two phases helps to: (1) provide more electrochemical active sites to promote the insertion / extraction reaction of sodium ions; (2) accelerate electron transport through abundant heterogeneous phase interfaces.
[0126] The specific surface area and pore structure of SnS / CoS-5 were characterized by nitrogen adsorption-desorption isotherm test. Figure 4 The following are nitrogen adsorption-desorption isotherms and pore size distribution diagrams for SnS / CoS-5; where (a) is the nitrogen adsorption-desorption isotherm and (b) is the pore size distribution diagram.
[0127] according to Figure 4 The calculated specific surface area of SnS / CoS-5 is 31 m². 2 / g, pore volume 0.08cm 3 The pore size distribution ( / g) confirms the existence of mesopores ranging from 2-50 nm, with an average pore size of 11.08 nm, indicating that the material retains a certain pore structure during sulfidation. This is mainly because thiourea produces H2S gas after high-temperature decomposition, which has a certain etching effect on the material. The nitrogen adsorption-desorption curves of SnS / CoS-5 are shown in... The presence of a significant hysteresis loop confirms that SnS / CoS-5 exhibits a typical type IV isotherm in mesoporous materials. The abundance of mesopores facilitates contact between the electrode and the electrolyte, as well as the diffusion of sodium ions within the material. However, the low specific surface area may also have adverse effects, such as insufficient exposure of active sites and limited reaction sites between sodium ions and the material, potentially restricting specific capacity, especially at high current densities, where rate performance may be limited.
[0128] 2. Test results of Example 2: Figure 5The images are SEM images and elemental surface scans; (a)-(c) are SEM images of SnS / CoS@NC-0.007 at different magnifications, (d) is the particle size distribution of SnS / CoS@NC-0.007, (e)-(g) are SEM images of SnS / CoS@NC-0.010 at different magnifications, (h) is the particle size distribution of SnS / CoS@NC-0.010, (i)-(k) are SEM images of SnS / CoS@NC-0.013 at different magnifications, (l) is the particle size distribution of SnS / CoS@NC-0.013, and (m) is the elemental surface scan of SnS / CoS@NC-0.010.
[0129] from Figure 5 As shown in (a)-(d), SnS / CoS@NC-0.007 exhibits a uniform nanocubic structure with an average particle size of approximately 111.7 nm, clear particle outlines, and weak aggregation. Figure 5 As shown in (e)-(h), SnS / CoS@NC-0.010 still maintains a regular cubic morphology, with the average particle size increasing to approximately 181.4 nm. Figure 5 As can be seen in (i)-(l), the average particle size of SnS / CoS@NC-0.013 increases significantly to about 377.1 nm, the edges of the cubic structure gradually become rounded, the particle agglomeration phenomenon is significantly aggravated, and even cubic framework collapse and particle fusion behavior occur. This may be due to the excessive PDA coating, which causes adhesion during high-temperature pyrolysis, weakens the structural confinement effect, makes it difficult to effectively constrain particle growth, and causes agglomeration between particles, which is not conducive to sodium ion transport and electrochemical performance optimization.
[0130] To verify the elemental distribution of the anode material, the elemental surface scan of SnS / CoS@NC-0.010 is shown below. Figure 5 As shown in (m). The results show that Co, Sn, and C are uniformly distributed throughout the region without significant aggregation. This also indicates that PDA was successfully derived into NC during the sulfidation process. In summary, the DA concentration parameter has a regulatory effect on the morphology and structure of SnS / CoS@NC. A suitable DA concentration (0.010 mol / L) can maintain a uniform nanocubic structure while providing a complete carbon coating layer, providing a good structural basis for the performance optimization of the anode material.
[0131] TEM images further revealed the microstructure of SnS / CoS@NC at different DA concentrations. Figure 6The images are TEM images, HR-TEM images, elemental surface scans, and energy dispersive spectroscopy (EDS). Among them, (a) is the TEM image of SnS / CoS@NC-0.007, (b) is the TEM image of SnS / CoS@NC-0.013, (c) is the TEM image of SnS / CoS@NC-0.010, (d) is a magnified view of (c), (e) is the HR-TEM image of SnS / CoS@NC-0.010, (f) is the elemental surface scan of SnS / CoS@NC-0.010, and (g) is the EDS of SnS / CoS@NC-0.010.
[0132] from Figure 6 In (a), it can be clearly observed that SnS / CoS@NC-0.007 exhibits a small nanocubic structure, consistent with the average particle size of 111.7 nm obtained from SEM. The overall particle outline is clear, with a thin carbon layer covering the edges, and some areas not completely coated. Figure 6 (b) clearly shows a significant increase in the particle size of SnS / CoS@NC-0.013, which is basically consistent with the average particle size of 377.1 nm statistically obtained from SEM. The particle edges are rounded, the carbon coating thickness is uneven, and particle agglomeration is significantly aggravated. Figure 6 (c) shows that the SnS / CoS@NC-0.010 particles have a moderate size and a uniform and relatively complete carbon coating layer; under magnification, a carbon layer of about 5-10 nm thickness can be clearly observed. Figure 6 (d) Its continuous and uniform coating structure can effectively buffer the volume expansion of SnS / CoS during the sodiumification / desodiumification process, and also provide a good electron transport channel. Figure 6 In (e), multiple lattice fringes are clearly visible. The lattice fringes with interplanar spacings of 0.404 nm and 0.212 nm match well with the (110) and (210) crystal planes of the orthorhombic SnS. The lattice fringes with interplanar spacings of 1.412 nm and 0.292 nm correspond to the (112) and (100) crystal planes of the cubic CoS system, respectively. These interplanar spacings closely match those of the standard PDF card and correspond to the crystal phases of SnS / CoS-5 lattice fringes, confirming the successful synthesis of SnS and CoS with good crystallinity; from Figure 6 In (e), a clear two-phase interface can be observed in SnS / CoS@NC-0.010. According to... Figure 6(f) The elemental surface scan of SnS / CoS@NC-0.010 shows that S is uniformly distributed, while Sn and Co are concentrated, indicating that the SnS and CoS phases are non-uniformly distributed in the nanocubes, similar to a Janus structure. Each nanocube can be considered as a Janus SnS / CoS heterostructure cell. Furthermore, C and N are observed to be uniformly distributed around the nanocubes, indicating that an NC layer was successfully coated on the surface of the SnS / CoS nanocubes. Figure 6 (g) shows that the C content of SnS / CoS@NC-0.010 is 16.56wt% and the N content is 6.34wt%; the elemental contents of S, Co and Sn are 23.12wt%, 24.31wt% and 29.66wt% respectively, indicating that the sulfidation reaction is relatively complete.
[0133] The formation of the Janus SnS / CoS heterostructure may be related to the transformation reaction of SnS2 and the different nucleation and growth rates of SnS and CoS under sulfidation heat treatment conditions. During sulfidation, H2S first reacts with tin and cobalt components to generate SnS2 and CoS. Some SnS2 melts and adheres to the inner surface of the PDA-derived carbon layer, while CoS remains stable after formation without phase transition or state change. Simultaneously, when SnS2 solidifies, it is reduced to SnS, leading to phase separation of SnS and CoS, thus forming a Janus heterostructure with distinct phase boundaries within the SnS / CoS nanocubes. Therefore, the spatial confinement effect of the PDA-derived carbon layer is crucial for the formation of the Janus heterostructure.
[0134] Figure 7 The XRD spectra of SnS / CoS@NC-0.007, SnS / CoS@NC-0.010, and SnS / CoS@NC-0.013 are shown. Spectral analysis clarifies the crystal structure and its properties. The diffraction peaks at 2θ = 21.9°, 26.02°, 27.5°, 32.01°, 39.05°, and 45.50° correspond to the (110), (120), (021), (040), (131), and (150) crystal planes of orthorhombic SnS, respectively. The characteristic peaks at 2θ = 30.54°, 35.26°, 46.8° and 54.28° correspond to the (100), (101), (102) and (110) crystal planes of cubic CoS. It can also be seen that as the DA concentration increases, the carbon layer thickens, sulfidation becomes incomplete, and the peak intensity of sulfides, especially CoS, weakens. Notably, changing the DA concentration does not alter the position of the main peak, and it is consistent with the diffraction peak position of SnS / CoS-5, further proving that PDA coating and subsequent sulfidation processes do not change the crystal structure of the material.
[0135] Figure 8 The nitrogen adsorption-desorption isotherms and pore size distribution diagrams for SnS / CoS@NC-0.010 are shown; where (a) is the nitrogen adsorption-desorption isotherm and (b) is the pore size distribution diagram.
[0136] The specific surface area of SnS / CoS@NC-0.010 reaches 42 cm². 2 / g, pore volume is 0.26cm 3 / g, with an average pore size of 8.28nm. (From...) Figure 8 As can be seen, SnS / CoS@NC-0.010 exhibits typical Type IV characteristics, accompanied by an H3-type hysteresis loop, indicating that it is a mesoporous material. Compared with SnS / CoS-5, SnS / CoS@NC-0.010 shows a relatively high specific surface area. This phenomenon is mainly attributed to: firstly, the formation of unique Janus heterostructure SnS / CoS nanocube particles, which lays the foundation for the increase in specific surface area; secondly, the surface of the CoSn(OH)6 precursor coated with PDA, whose NC shell formed after pyrolysis not only increases the surface roughness of the material but also further enhances the specific surface area; in addition, the carbon-doped layer introduces defects and functional groups on the surface of SnS / CoS particles, which also contributes to the increase in specific surface area. The increased pore volume can accommodate the volume expansion of SnS, preventing the material structure from collapsing, thereby improving electrochemical stability. The relatively high specific surface area can expose more sodium storage active centers, promoting sodium ion insertion / extraction and rapid charge transport, thus improving the electrochemical kinetics of the material. Ultimately, this achieves a significant optimization of the overall electrochemical performance of SnS.
[0137] 3. Test results of Examples 3-5: Figure 9 These are SEM images and elemental surface scans; where (a)-(d) are SEM images of SnS / CoS@NC-CNFs(P) at different magnifications, (e)-(h) are SEM images of SnS / CoS@NC-CNFs(E) at different magnifications, (i)-(l) are SEM images of SnS / CoS@NC-CNFs(C) at different magnifications, and (m) is an elemental surface scan of SnS / CoS@NC-CNFs(C). Figure 9As can be seen from (a)-(d), SnS / CoS@NC-CNFs(P) exhibits a three-dimensional interconnected carbon nanofiber (CNFs) network framework, but the number of loaded SnS / CoS@NC particles is relatively small, and the fiber surface is relatively bare. Figure 9 As can be seen from (e)-(h), the SnS / CoS@NC particle loading is significantly improved, and the particle density is significantly increased, but there is still particle stacking in local areas. From Figure 9 As can be seen from (i)-(l), the three-dimensional network skeleton of CNFs is completely preserved, the particles are relatively uniformly dispersed and have a relatively regular morphology. The particles are tightly attached to the surface of the fiber skeleton and do not form large agglomerates, thus fully preserving the ion transport pores. Figure 9 (m) shows that in SnS / CoS@NC-CNFs(C), Sn and Co elements are relatively uniformly distributed on the surface of C nanofibers, with no obvious local aggregation of elements. C elements run through the entire network, serving as a continuous conductive substrate to ensure efficient electron transport.
[0138] Figure 10 The images are TEM images; (a)-(c) are TEM images of SnS / CoS@NC-CNFs(P) at different magnifications, (d)-(f) are TEM images of SnS / CoS@NC-CNFs(E) at different magnifications, and (g)-(i) are TEM images of SnS / CoS@NC-CNFs(C) at different magnifications. Figure 10 In (a)-(c), SnS / CoS@NC-CNFs(P) only exhibits a sheet-like, wrinkled structure composed of cellulose-derived carbon nanofibers, without obvious active material loading, proving that pure physical adsorption cannot effectively anchor CoSn(OH)6@PDA. Figure 10 As can be seen from (d)-(f), SnS / CoS@NC-CNFs(E) can achieve a certain amount of active material loading through electrostatic interaction, but the loading capacity is limited. From... Figure 10 As can be seen in (g)-(i), in SnS / CoS@NC-CNFs(C), fibers with a diameter of about 50-100 nm are intertwined, and the surface is loaded with a large number of dense SnS / CoS@NC nanoparticles. This proves that SnS / CoS@NC-CNFs(C) prepared by the covalent bonding strategy can achieve higher loading of active material anchoring, while retaining the network channels of carbon nanofibers, providing a structural basis for excellent electrochemical performance.
[0139] The crystal structure and properties of the material were analyzed and elucidated using XRD spectra. Figure 11XRD spectra of SnS / CoS@NC-CNFs (P), SnS / CoS@NC-CNFs (E), and SnS / CoS@NC-CNFs (C). From... Figure 11 It can be seen that all three materials exhibit broad peaks in the 10-20° range, corresponding to the amorphous carbon structure of the CNFs substrate, proving the existence of carbon networks in the materials. Furthermore, the diffraction peaks at 2θ = 26.02°, 27.50°, 32.01°, 39.05°, and 45.50° correspond to the (120), (021), (040), (131), and (150) crystal planes of orthorhombic SnS, respectively. The characteristic peaks at 2θ = 30.54°, 35.26°, 46.80° and 54.28° correspond to the (100), (101), (102) and (110) crystal planes of the cubic CoS system. This demonstrates the introduction of SnS and CoS components. Furthermore, it can be observed that the relative intensities of the diffraction peaks of SnS and CoS in SnS / CoS@NC-CNFs(C) are increased, but the crystal form remains unchanged.
[0140] Figure 12 The nitrogen adsorption-desorption isotherms and pore size distribution diagrams of SnS / CoS@NC-CNFs(C) are shown; where (a) is the nitrogen adsorption-desorption isotherm and (b) is the pore size distribution diagram.
[0141] The specific surface area of SnS / CoS@NC-CNFs(C) is 10.0 cm². 2 / g, pore volume is 0.04cm 3 / g, with an average pore size of 40.52nm. The figure shows that SnS / CoS@NC-CNFs(C) exhibits a type IV isotherm. The isotherm characteristics at low relative pressure (P / P0 < 0.1) indicate the presence of mesopores, and the hysteresis loops with P / P0 in the 0.4-1.0 range also reveal crack-like mesoporous structure characteristics due to voids between nanofiber aggregates. The reduced specific surface area and pore volume are mainly attributed to the assembly of CoSn(OH)6@PDA in the three-dimensional network porous structure, leading to a significant reduction in micropores. This structure optimizes the material's volumetric energy density and other properties, while reducing interfacial side reactions between the electrolyte and the material, and improving the first-cycle coulombic efficiency. The retention of some mesoporous structures and the macroporous structure introduced by cellulose can alleviate the volume expansion of the loaded particles during charge-discharge cycling, improving the structural stability of the material.
[0142] Figure 13 The FTIR spectra are shown below; (a) is the FTIR spectrum of SnS / CoS@NC-CNFs(C), and (b) is the FTIR spectrum of SnS / CoS@NC-CNFs(E).
[0143] from Figure 13 As can be seen from (a): 3100cm -1 The broad and gentle absorption peak at 1570 cm⁻¹ is a typical signal of oxygen / nitrogen-containing functional groups, corresponding to the stretching vibration of the OH / NH bond; -1 This corresponds to the Schiff base C=N double bond generated by the reaction of aldehyde-modified cellulose with PDA, and the sp... 2 C=C skeletal vibrations and the bending vibrations of NH4+ from amino residues. 1441 cm -1 The absorption peak at 1107 cm⁻¹ originates from the CN bonds in nitrogen-doped carbon. -1 The absorption peak at 500 cm⁻¹ belongs to the Si-OC stretching vibration formed after triethoxysilylbutyral was modified on the fiber surface. The silicon-oxygen bond acts as a connecting bridge anchored on the cellulose-derived carbon surface, proving the success of silane modification. -1 The absorption peaks on the left and right sides originate from the Sn-S / Co-S stretching vibration, directly proving the successful loading of SnS / CoS nanoparticles.
[0144] contrast Figure 13 (a) It can be seen that: Figure 13 (b) is located at 1069cm -1 The CO bonds corresponding to the cellulose residues are slightly different from those of SnS / CoS@NC-CNFs(C); at 1455 cm⁻¹ -1 The infrared absorption peak originates from the NH bending vibration and CN stretching vibration in the amide, and its wavenumber is affected by the amino group in PEI; 480 cm⁻¹ -1 The absorption peaks around the left and right originate from the Sn-S / Co-S stretching motion; this indicates that both methods successfully achieved the loading of SnS / CoS nanoparticles. Among them, SnS / CoS@NC-CNFs(C) prepared from aldehyde-modified cellulose retains a small amount of C=N and has Si-OC bonds, which can make the interface structure more stable through chemical bonding.
[0145] To verify the self-assembly of electrostatic adsorption, Zeta potential tests were performed on CoSn(OH)6@PDA, cellulose filter paper@PEI (i.e., PEI-modified filter paper), and the entire CoSn(OH)6@PDA-cellulose filter paper@PEI mixture (i.e., the product obtained in step II-2 of Example 4). Figure 14As shown, the Zeta potential test results indicate that CoSn(OH)6@PDA nanoparticles are negatively charged (approximately -11 mV) in aqueous solution, while the cellulose filter paper@PEI surface exhibits a strong positive charge (approximately +11 mV). After electrostatic adsorption assembly, the Zeta potential of CoSn(OH)6@PDA-cellulose filter paper@PEI becomes approximately -4 mV, and the negative charge is significantly reduced. This demonstrates that the positive and negative charge attraction mediated by PEI successfully achieved stable loading of CoSn(OH)6@PDA on the cellulose filter paper, laying the foundation for the subsequent high-temperature one-step vulcanization preparation of SnS / CoS@NC-CNFs(E).
[0146] III. Sodium storage performance test: Cyclic voltammetry (CV) testing: The core of cyclic voltammetry lies in applying a triangular waveform pulsed voltage to the working electrode, controlling the electrode potential to oscillate back and forth at a constant rate between set upper and lower limits. This process induces a redox reaction on the electrode surface, thereby generating a current response. In this experiment, the instrument used for cyclic voltammetry testing was a Shanghai Chenhua CHI660E electrochemical workstation. A voltage range of 0.01–3.0 V and a scan rate of 0.1 mV / s were set, and three charge-discharge cycles were performed to obtain CV curve data.
[0147] Constant current charge-discharge test: The constant current charge-discharge test is an important electrochemical testing method. It involves charging and discharging electrodes under constant current conditions and recording the voltage change over time to evaluate the electrochemical performance of the electrode material. This invention utilizes Shenzhen Xinwei... The battery was tested using a testing system with a voltage range of 0.01~3.0V at room temperature. The current density was fixed at 100mA / g (0.1C), 0.2C, 0.5C, and 1C.
[0148] Electrochemical impedance spectroscopy (EIS) measurement: In the Nyquist plot, the horizontal axis represents the real part (Z′), and the vertical axis represents the imaginary part (Z″). The Nyquist plot consists of two parts: the semi-circular portion in the high-frequency region corresponds to the interfacial transport confinement process, representing the charge transfer resistance (Ro) of the electrode surface. ct The value is the same as the diameter of the semicircle, and the linear part in the low-frequency region corresponds to the diffusion-limited process. The instrument used in this experiment is the Shanghai Chenhua CHI660E electrochemical workstation, with the frequency range parameter set to 100000-0.1Hz, the scanning mode to FT, and the test voltage amplitude to 5mV.
[0149] Test results: 1. Test results of Example 1 (SnS / CoS-3, SnS / CoS-4, SnS / CoS-5, SnS / CoS-6) and Comparative Example 1 (SnS) and Comparative Example 2 (CoS): In the range of 0.01-3.0V (vs. Na / Na) + The first three cycles of CV curve testing were performed at a voltage window and a scan rate of 0.1 mV / s. Figure 15 The CV curves are for SnS / CoS, pure SnS, and pure CoS; where (a) is the CV curve for SnS / CoS-3, (b) is the CV curve for SnS / CoS-4, (c) is the CV curve for SnS / CoS-5, (d) is the CV curve for SnS / CoS-6, (e) is the CV curve for pure SnS, and (f) is the CV curve for pure CoS.
[0150] Depend on Figure 15 It can be seen that the CV curves of all materials exhibit typical conversion reaction characteristics, showing multi-step sodium insertion and extraction reactions.
[0151] Constant current charge-discharge curve tests were conducted at a current density of 100 mA / g for cycles 1, 2, 5, 10, 50, and 100. Figure 16 The constant current charge-discharge curves are for SnS / CoS, pure SnS, and pure CoS; where (a) is the constant current charge-discharge curve for SnS / CoS-3, (b) is the constant current charge-discharge curve for SnS / CoS-4, (c) is the constant current charge-discharge curve for SnS / CoS-5, (d) is the constant current charge-discharge curve for SnS / CoS-6, (e) is the constant current charge-discharge curve for pure SnS, and (f) is the constant current charge-discharge curve for pure CoS.
[0152] Figure 16 In the process, the charge-discharge curves maintained almost the same shape and voltage plateau. A clear plateau can be seen in the discharge curve of the first cycle at around 1V, which may be due to sodium ion insertion into CoS to form Na. x CoS. The voltage plateau at 0.4V corresponds to a further alloying reaction to form Na. x The Sn process. During the first charging cycle, there are two distinct charging plateaus at 1.19V and 1.75V, corresponding to the formation of CoS. The voltage plateau near 0.75V indicates the presence of Na. x The dealloying reaction of Sn was observed. This is in good agreement with the initial oxidation peak potential observed in the CV test. Among them, SnS / CoS-5 exhibited a high initial discharge specific capacity of 749.0 mAh / g and an initial coulombic efficiency of 48.8%. The irreversible capacity loss in the first cycle is likely mainly due to the low reversibility of the initial conversion reaction of SnS sodium ion insertion and the formation of the SEI film.
[0153] Figure 17Cyclic performance curves of different negative electrode materials under constant current charge-discharge at a current density of 100 mA / g (1C) are shown. Among them, (a) is the cycle performance curve of SnS / CoS in Example 1 and the coulombic efficiency curve of SnS / CoS-5, and (b) is the cycle performance curve of pure SnS in Comparative Example 1 and pure CoS in Comparative Example 2.
[0154] like Figure 17 As shown in (a), the capacity decay of SnS / CoS (SnS / CoS-3, SnS / CoS-4, SnS / CoS-5, and SnS / CoS-6) mostly occurs in the first 60 cycles, possibly due to the insertion of large-radius sodium ions, limited sodium ion capacity, and irreversible side reactions on the surface, which increase the capacity loss in the first half of the cycle. Among them, SnS / CoS-5 has a basically stable capacity after 60 cycles and can maintain a coulombic efficiency of over 98%. After 200 cycles, it exhibits the highest reversible specific capacity of 229.1 mAh / g, with a capacity retention of 30.6%. The mesoporous structure of SnS / CoS-5 causes sodium ions in the electrolyte to gradually diffuse into the material pores. Surface side reactions cause a significant capacity decay in the early stage, but at the same time, it plays a certain role in buffering the mechanical stress damage caused by the repeated expansion / contraction of the metal sulfide volume in the later stage. In addition, the uniformly distributed heterostructure in SnS / CoS-5 promotes charge transfer. After 200 cycles, Figure 17 In (b), the charge-discharge capacity of pure SnS decayed to 33.0 mAh / g, with a capacity retention rate of only 7.5%; pure CoS also showed an extremely low capacity retention rate. Figure 17 In (a) and (b), the charging cycle curve and the discharging cycle curve basically overlap, which is because the charging and discharging tend to be stable after the sodium insertion and deintercalation in the first few cycles.
[0155] Constant current charge-discharge test by changing the current density; Figure 18 The following are rate performance curves for different anode materials; (a) is the rate performance curve of SnS / CoS (SnS / CoS-3, SnS / CoS-4, SnS / CoS-5, SnS / CoS-6) in Example 1, and (b) is the rate performance curve of pure SnS and pure CoS.
[0156] Depend on Figure 18 (a) It can be seen that the average discharge specific capacity of SnS / CoS-5 at 0.1C, 0.2C, 0.5C, 1C (1C=1000mA / g) and back to 0.1C is 331.9mAh / g, 176.4mAh / g, 132.5mAh / g, 117.7mAh / g and 220.2mAh / g, respectively, which are all much higher than those of pure SnS and pure CoS. Figure 18(b) The limited capacity of SnS / CoS-5 after charge-discharge at different rates is mainly due to the intensified volume expansion of SnS under high-rate charge-discharge, causing partial structural collapse and damage. For example... Figure 18 As shown in (b), the capacity of pure SnS drops to almost 0 mAh / g at 1C rate. This comparison demonstrates that constructing a two-component metal sulfide with CoS can, to some extent, maintain the structural stability and high-rate specific capacity of SnS after rapid sodium insertion / extraction. Figure 18 In (a) and (b), the charging cycle curve and the discharging cycle curve basically overlap after charging and discharging at a rate of 0.1C, which is because the charging and discharging tends to be stable.
[0157] The experimental results are summarized in the table below, and the main experimental data are as follows: Table 1
[0158] The electrode kinetics of SnS / CoS, pure SnS, and pure CoS were systematically characterized by electrochemical impedance spectroscopy (EIS). The semicircles in the high-frequency region of the EIS (Nyquist curve) correspond to the charge transfer resistance (Ro) at the electrode / electrolyte interface. ct ) and double-layer capacitance (CPE), the oblique line in the low-frequency region corresponds to the diffusion process of sodium ions inside the electrode, i.e., the Warburg impedance ( The intercept between the high-frequency region and the real part represents the battery's bulk resistance. ).
[0159] Figure 19 Electrochemical impedance spectroscopy (EIS) results for SnS / CoS, pure SnS, and pure CoS are shown; where (a) is the Nyquist curve, and (b) is the real part (Z') divided by the square root of the angular frequency (ω). -0.5 (c) is the linear relationship diagram in the low frequency region, and (d) is the equivalent analog circuit diagram.
[0160] Depend on Figure 19 (a) It can be seen that the Nyquist curve of all negative electrode materials consists of a semicircle in the high-frequency region and a sloping line in the low-frequency region.
[0161] To delve deeper into the dynamic mechanism, an equivalent analog circuit diagram was used in Zview software. Figure 19 (c) The Nyquist curve was fitted, and the fitting results are shown in Table 2. The R-values of SnS / CoS-3 were compared. ct (4832Ω), R of SnS / CoS-4 ct (4760Ω), R of SnS / CoS-5 ct (2056Ω), R of SnS / CoS-6 ct(2129Ω) It can be seen that the R of all SnS / CoS anode materials ct The resistance values are all significantly lower than those of SnS. ct (6023Ω) and CoS R ct The result (5853Ω) indicates that the SnS and CoS composite can effectively reduce the charge transport resistance at the electrode interface. However, when the proportion of the CoS phase is too high or too low, it will have an adverse effect. This phenomenon is mainly attributed to the synergistic effect between the two components, and the construction of a rich heterojunction interface effectively promotes the interfacial charge transfer.
[0162] Sodium ion diffusion coefficient ( The unit of measurement is cm. 2 / s) and Warburg coefficient (σ, measured in Ω s) -0.5 The square of the anode material is inversely proportional to the square of the anode material. According to formula (1), the anode material of each anode material can be calculated from the low-frequency region data of the Nyquist curve. .
[0163] (1); In the above formula: R is the gas constant (8.314 J / mol / K), T is the absolute temperature (K), and A is the cross-sectional area of the electrode active material (cm²). 2 ), where n is the number of electrons transferred in the redox reaction (dimensionless), F is the Faraday constant (96485 C / mol), and C is the sodium ion concentration (mol / cm³). 3 ).
[0164] Depend on Figure 19 (b) It can be seen that the slope of the fitted line of SnS / CoS-5 material is the smallest, while SnS and CoS have larger slopes of the fitted line, and the slope of the fitted line of SnS / CoS-3 material is the largest, which may be related to its regular surface and lack of porous structure.
[0165] Table 2 lists the σ values for each negative electrode material and their corresponding values. As shown in the table, SnS / CoS⁻⁵ has the lowest σ value (828.6 Ω·s). -0.5 ), The maximum is 6.31 × 10 -18 cm 2 / s.
[0166] Table 2. Fitted values of electrochemical kinetic parameters for SnS / CoS, pure SnS, and pure CoS.
[0167] 2. Test results of Example 2: Figure 20For SnS / CoS@NC at 0.01-3.0V (vs. Na / Na + The CV curves of the first three cycles performed at a voltage window and a scan rate of 0.1 mV / s are shown. Among them, (a) is the CV curve of SnS / CoS@NC-0.007, (b) is the CV curve of SnS / CoS@NC-0.010, and (c) is the CV curve of SnS / CoS@NC-0.013.
[0168] like Figure 20 As shown, in the first cathode scan, the peak at 0.9–1.2 V corresponds to the pre-intercalation of sodium ions at the SnS / CoS Janus heterojunction interface: And the defect sites introduced by pyridine nitrogen and pyrrole nitrogen on the NC surface for Na + Adsorption of Co occurs at approximately 0.7V. 2+ and Sn 2+ The processes of reduction to elemental Co and elemental Sn, respectively, and the formation process of the SEI film.
[0169] Especially Figure 20 In (b), the strongest reduction peak in the first ring can be seen at about 0.4V, corresponding to the formation of Na during the tin-sodium alloying process. y Sn. In the first anodic scan, two consecutive oxidation peaks at 0.26 V and 0.75 V correspond to Na. y The two-step process of Sn dealloying to generate elemental Sn: The broad oxidation peak between 1.0 and 1.5 V corresponds to Na. x The regeneration of CoS; the strong oxidation peak between 1.5 and 2.0 V corresponds to the insertion / extraction of sodium ions, i.e. The process of re-oxidation to CoS was observed. Subsequent cycling tests showed that the CV curves of SnS / CoS@NC exhibited high overlap after the second cycle. In particular, the redox peaks of SnS and CoS in SnS / CoS@NC-0.010 remained prominent, demonstrating the material's excellent reversibility of sodium ion insertion / extraction and cycling stability. Compared to SnS / CoS-5, the carbon layer acts as a physical barrier, buffering the volume expansion of SnS / CoS-5 during sodium storage and preventing the pulverization of the active material and the collapse of the electrode structure. Therefore, the peak shapes in the second and third cycles are more stable and have a higher degree of overlap.
[0170] To further investigate the electrochemical behavior of the electrode, constant current charge-discharge curve tests were performed on the negative electrode material of Example 2. Figure 21The constant current charge-discharge curves of SnS / CoS@NC are shown below; (a) is the constant current charge-discharge curve of SnS / CoS@NC-0.007, (b) is the constant current charge-discharge curve of SnS / CoS@NC-0.010, and (c) is the constant current charge-discharge curve of SnS / CoS@NC-0.013.
[0171] In the discharge curves, the voltage plateau and slope at 0.7–0.9 V correspond to the reduction to elemental Co and Sn, as well as the formation of the SEI film, consistent with the CV curves. SnS / CoS@NC-0.010 exhibits high initial charge-discharge specific capacities of 443.8 mAh / g and 861.4 mAh / g, respectively, with an initial coulombic efficiency of 51.5%. The high overlap of the SnS / CoS@NC-0.010 curves indicates good reversibility of the electrode.
[0172] Figure 22 Figures show the test results of the cycling performance and rate performance of SnS / CoS@NC; (a) shows the cycling performance curve of SnS / CoS@NC and the coulombic efficiency curve of SnS / CoS@NC-0.010, (b) shows the comparison of discharge specific capacity of the first cycle and the 200th cycle, (c) shows the rate performance curve of SnS / CoS@NC, and (d) shows the comparison of the average discharge specific capacity at 1C rate and the return to 0.1C rate.
[0173] Depend on Figure 22 (a)-(b) show that SnS / CoS@NC-0.010 exhibits the highest initial discharge specific capacity (861.4 mAh / g) and initial coulombic efficiency (51.5%). The capacity loss in the first cycle is likely related to the unavoidable depletion of the SEI film. After 200 cycles, the reversible specific capacity of SnS / CoS@NC-0.010 is 342.1 mAh / g, with a capacity retention of 39.7%. The decrease in specific capacity of SnS / CoS@NC-0.010 mainly occurs in the initial stage of the first 50 cycles, which may be due to insufficient sodium insertion and polarization in the early stages of charge and discharge. Figure 22 (a) The charging cycle curve and the discharging cycle curve basically overlap, which is because the charging and discharging tend to be stable after sodium insertion and deintercalation in the first few cycles.
[0174] Compared to SnS / CoS-5, SnS / CoS@NC-0.010 showed improved electrochemical performance in cycling tests. This is attributed to the following reasons: First, the introduction of CoS and uniform coating of the NC layer resulted in a more stable microstructure; second, each nanocube can construct a Janus SnS / CoS heterostructure, and the resulting built-in electric field effectively promotes carrier transport and reaction kinetics. The initial coulombic efficiencies of SnS / CoS@NC-0.007 and SnS / CoS@NC-0.013 were 42.1% and 49.2%, respectively. This demonstrates that the appropriately thick and uniformly intact NC layer coating maintains good dispersion of the SnS / CoS nanocube particles, thus effectively improving the cycling performance of the electrode material.
[0175] Depend on Figure 22 From (c)-(d), it can be seen that the average discharge specific capacity of SnS / CoS@NC-0.010 at different rate levels (0.1C, 0.2C, 0.5C, 1C, and 0.1C return) is 508.6 mAh / g, 395.8 mAh / g, 296.2 mAh / g, 199.1 mAh / g, and 389.6 mAh / g, respectively, which is higher than the average discharge specific capacity of SnS / CoS-5 at each rate level (331.9 mAh / g, 176.4 mAh / g, 132.5 mAh / g, 117.7 mAh / g, and 220.2 mAh / g). The rate performance and cycle performance of each anode material follow the same pattern. Figure 22 (b) and (d)). Figure 22 (c) The charging cycle curve and the discharging cycle curve basically overlap after charging and discharging at a rate of 0.1C, which is because the charging and discharging tends to be stable.
[0176] The specific capacity of SnS / CoS@NC-0.010 at high current density is significantly improved compared to SnS / CoS-5 in Example 1. The main reasons are as follows: First, the refined Janus nanostructure and enhanced charge transfer significantly enhance the conversion and alloying reaction kinetics and reversibility of SnS. Second, the introduction of CoS improves the conductivity of the material, and the defects introduced by nitrogen-doped carbon provide more sodium ion transport channels, optimizing the diffusion kinetics of sodium ions. Third, the NC layer coating improves conductivity while effectively protecting the SnS / CoS heterostructure from collapse during rapid charge and discharge, exhibiting better electrochemical reaction kinetic performance.
[0177] The experimental results above were summarized, and the corresponding performance of SnS / CoS@NC-0.002 and SnS / CoS@NC-0.018 was tested using the same method. The main experimental results are shown in the table below: Table 3
[0178] The kinetic properties of SnS / CoS@NC were systematically characterized by electrochemical impedance spectroscopy. Figure 23 The electrochemical impedance spectroscopy (EIS) results for SnS / CoS@NC are shown; (a) is the Nyquist curve, and (b) is the square root of the real part (Z') with respect to the angular frequency (ω). -0.5 (c) is the linear relationship diagram in the low frequency region, and (d) is the equivalent analog circuit diagram.
[0179] From the equivalent analog circuit diagram ( Figure 23 (c) The R-value of SnS / CoS@NC-0.007 was obtained by fitting. ct (2190Ω), R of SnS / CoS@NC-0.010 ct (1524Ω), R of SnS / CoS@NC-0.013 ct (1990Ω), it can be seen that the R of SnS / CoS@NC-0.010 is... ct The lowest resistance indicates that constructing a suitable thickness and uniform, complete NC layer coating can increase conductivity and reduce interfacial charge transport resistance. However, when the carbon layer coating thickness is too large, leading to agglomeration, or when the coating amount is too small and cannot be uniformly distributed, the modification effect is poor. Furthermore, compared to SnS / CoS-5, the unique Janus heterostructure formed by SnS / CoS@NC-0.010 also promotes efficient interfacial charge transport. Figure 23 (b) It can be seen that the slope of the fitted line of SnS / CoS@NC-0.010 material is the smallest, which corresponds to the smallest internal material ion diffusion resistance and the strongest ion diffusion kinetic performance.
[0180] Table 4 lists the σ values for each negative electrode material and their corresponding values. As shown in the table, the σ value of SnS / CoS@NC-0.010 is the lowest (702.1 Ω s). -0.5 ),corresponding The maximum is 8.78 × 10 -18 cm 2 / s. This is likely because the Janus heterostructure of the nanocubes, as well as the defects and rough surfaces of the NC coating, facilitate the diffusion of sodium ions.
[0181] Table 4 Fitted values of electrochemical kinetic parameters for SnS / CoS@NC
[0182] Figure 24The images are SEM images of SnS / CoS@NC-0.010 and SnS / CoS-5 after 200 cycles at 0.1C; where (a) and (b) are SEM images of SnS / CoS@NC-0.010 after 200 cycles at different magnifications, and (c) and (d) are SEM images of SnS / CoS-5 after 200 cycles at different magnifications.
[0183] Depend on Figure 24 As can be observed in (a) and (b), SnS / CoS@NC-0.010 maintains a complete and uniform structural morphology after 200 cycles, indicating excellent structural stability. However, as... Figure 24 As shown in (c) and (d), significant structural changes were clearly observed after 200 cycles of SnS / CoS-5, with severe pulverization and even signs of localized structural collapse. This phenomenon further confirms the crucial role of the Janus heterostructure's two-phase interface stability and the NC layer coating in the material's sodium intercalation / deintercalation structural stability. The two modification strategies synergistically effectively suppress the structural damage caused by SnS volume expansion during charging and discharging, jointly supporting the mechanism for improving the material's sodium storage performance.
[0184] In addition, the surface morphology of the electrode sheet was characterized before cycling and after 200 cycles at 0.1C. Figure 25 SEM images of different electrode sheets before and after cycling are shown below; (a) is the SEM image of SnS / CoS@NC-0.010 electrode sheet before cycling, (b) is the SEM image of SnS / CoS@NC-0.010 electrode sheet after 200 cycles, (c) is the SEM image of SnS / CoS@NC-0.007 electrode sheet before cycling, (d) is the SEM image of SnS / CoS@NC-0.007 electrode sheet after 200 cycles, (e) is the SEM image of SnS / CoS@NC-0.013 electrode sheet before cycling, (f) is the SEM image of SnS / CoS@NC-0.013 electrode sheet after 200 cycles, (g) is the SEM image of SnS / CoS-5 electrode sheet before cycling, and (h) is the SEM image of SnS / CoS-5 electrode sheet after 200 cycles.
[0185] Depend on Figure 25 (a) It can be seen that the surface of the SnS / CoS@NC-0.010 electrode sheet is flat and dense; Figure 25 In (b), the SnS / CoS@NC-0.010 electrode showed no obvious cracks, particle agglomeration, or detachment after cycling. Figure 25 As can be seen from (c)-(f), local cracks and particle agglomeration appear after SnS / CoS@NC-0.007 and SnS / CoS@NC-0.013 cycles, respectively. Figure 25(h) is a SEM image of the SnS / CoS-5 electrode sheet after cycling, which shows that there is a large area of collapse; indicating that the appropriate carbon layer thickness can effectively buffer the volume expansion and improve the stability of the electrode structure.
[0186] 3. Test results of Examples 3-5: Figure 26 The CV curves are shown below: (a) is the CV curve of SnS / CoS@NC-CNFs (P), (b) is the CV curve of SnS / CoS@NC-CNFs (C), and (c) is the CV curve of SnS / CoS@NC-CNFs (E). The CV curves are the first three cycles within a voltage window of 0.01–3.0 V (vs. Na / Na⁺) and a scan rate of 0.1 mV / s.
[0187] Depend on Figure 26 It can be seen that in the first cathode scan, the reduction peak at 0.9-1.2 V corresponds to the pre-intercalation reaction of sodium ions at the SnS / CoS Janus heterojunction interface. Compared to the pre-intercalation process of SnS / CoS@NC, the peaks are clearer and more pronounced, indicating that the porous structure of cellulose-derived carbon provides a smoother intercalation channel for sodium ions. A reduction peak appears at 0.7-0.9 V, located between the alloying peak and the pre-intercalation peak. This peak is broad and of moderate intensity, corresponding to Co. 2+ and Sn 2+ The conversion reaction to reduce to elemental metals and the formation of the SEI. The peak at approximately 0.4 V corresponds to the formation of Na in the tin-sodium alloying process. y Compared to the alloying peak of SnS / CoS@NC, Sn rapidly decays to a stable reversible peak in the second and third cycles. In the first anodic scan, a double peak appears at approximately 0.3 V and 0.7 V, corresponding to Na... y The two-step dealloying of Sn exhibits sharper, stronger, and clearer peaks compared to SnS / CoS@NC, indicating a more complete dealloying reaction. The strong oxidation peak near 1.75 V corresponds to the insertion / extraction of sodium ions, i.e., Na+. x The process of CoS oxidation to CoS shows that this peak appears stably in subsequent cycles. The good reversibility proves that the introduction of the cellulose-derived carbon skeleton and its anchoring of SnS / CoS effectively buffers the volume expansion during the sodium storage process, avoiding the pulverization of active materials and the collapse of the electrode structure.
[0188] Figure 27The constant current charge-discharge curves of SnS / CoS@NC-CNFs are shown below; (a) is the constant current charge-discharge curve of SnS / CoS@NC-CNFs (P), (b) is the constant current charge-discharge curve of SnS / CoS@NC-CNFs (C), and (c) is the constant current charge-discharge curve of SnS / CoS@NC-CNFs (E). Figure 27 It can be seen that the long voltage plateau appearing near 0.7V in the first discharge curve corresponds to the reduction to Co and Sn elements and the formation of the SEI film, consistent with the positions of the negative electrode materials in Examples 1 and 2. In the first charge curve, the voltage plateau appearing near 1.75V corresponds to the deintercalation and intercalation of sodium ions, consistent with the CV curve. The potential slope still exists after 100 cycles, demonstrating good reversibility of the electrode.
[0189] Figure 28 Figures show the cycle performance and rate performance test results of SnS / CoS@NC-CNFs; (a) shows the cycle performance curve of SnS / CoS@NC-CNFs and the coulombic efficiency curve of SnS / CoS@NC-CNFs (C), (b) shows the discharge specific capacity comparison between the first cycle and the 200th cycle, (c) shows the rate performance curve of SnS / CoS@NC-CNFs, and (d) shows the average discharge specific capacity comparison between 1C rate and 0.1C rate return.
[0190] Depend on Figure 28 As shown in (a) and (b), SnS / CoS@NC-CNFs(C) exhibits the best cycling performance, with a higher initial discharge specific capacity (951.2 mAh / g) and initial coulombic efficiency (69.3%) compared to the other two materials. After 200 cycles, its reversible specific capacity is 553.2 mAh / g, and its capacity retention is 58.2%. Figure 28 (a) The charging cycle curve and the discharging cycle curve basically overlap, which is because the charging and discharging tend to be stable after sodium insertion and deintercalation in the first few cycles.
[0191] Compared to SnS / CoS@NC-0.010, SnS / CoS@NC-CNFs(C) showed a significant improvement in various electrochemical performance parameters during cycling tests. This is primarily due to two reasons: firstly, the three-dimensional hierarchical network structure constructed from cellulose-derived carbon nanofibers provides space for the volume expansion of metal sulfides; secondly, SnS / CoS@NC-CNFs(C) utilizes Schiff base bonds to increase the loading of SnS / CoS@NC nanoparticles and enhance interfacial bonding. In contrast, the initial coulombic efficiencies of SnS / CoS@NC-CNFs(E) and SnS / CoS@NC-CNFs(P) were only 54.1% and 48.1%, respectively. Therefore, the method of chemically bonding the carbon network framework provides the best charge-discharge stability for SnS / CoS@NC nanoparticles.
[0192] Depend on Figure 28 From (c) and (d), we can see that the average discharge specific capacity of SnS / CoS@NC-CNFs(C) at different rates of 0.1C, 0.2C, 0.5C, 1C, and a return to 0.1C are 554.1 mAh / g, 413.2 mAh / g, 336.2 mAh / g, 211.9 mAh / g, and 461.3 mAh / g, respectively. The rate performance and cycle performance of each anode material follow the same pattern. Figure 28 (b) (d) Figure 28 (c) The charging cycle curve and the discharging cycle curve basically overlap after charging and discharging at a rate of 0.1C, which is because the charging and discharging tends to be stable.
[0193] The specific capacity of SnS / CoS@NC-CNFs(C) at high current densities is significantly improved compared to SnS / CoS@NC-0.010, mainly due to the following reasons: First, the continuous conductive network constructed by CNFs further shortens the electron transport path, greatly improving the kinetics and reversibility of SnS conversion and alloying reactions, and maintaining a relatively fast reaction rate even at high current densities. Second, the three-dimensional porous structure of CNFs further promotes electrolyte penetration and shortens the sodium ion diffusion distance, significantly optimizing the sodium ion diffusion kinetics, enabling the material to achieve rapid and sufficient electrochemical reactions even at high charge-discharge rates. Third, the chemical bonding of the loaded active particles and the dual protection of NC coating and CNFs framework make the material less prone to breakage and detachment during high charge-discharge processes, maintaining excellent electrochemical reaction kinetics.
[0194] The experimental results above were summarized, and the corresponding performance of SnS / CoS@NC-CNFs (C1) and SnS / CoS@NC-CNFs (C2) was tested using the same method. The main experimental results are shown in the table below: Table 5
[0195] The kinetic properties of SnS / CoS@NC-CNFs were systematically characterized by electrochemical impedance spectroscopy.
[0196] Figure 29 The electrochemical impedance spectroscopy (EIS) results for SnS / CoS@NC-CNFs are shown; (a) is the Nyquist curve, and (b) is the square root of the real part (Z') with respect to the angular frequency (ω). -0.5 (c) is the linear relationship diagram in the low frequency region, and (d) is the equivalent analog circuit diagram.
[0197] From the equivalent analog circuit diagram ( Figure 29(c) The R-value of SnS / CoS@NC-CNFs(P) was obtained by fitting. ct (2100Ω), R of SnS / CoS@NC-CNFs(C) ct (1234Ω) and R of SnS / CoS@NC-CNFs(E) ct (2050Ω); A comparison shows that the R of SnS / CoS@NC-CNFs(C) is... ct The lowest resistance value indicates that constructing a continuous conductive network and using covalent bonds for anchoring can reduce interfacial charge transport resistance and accelerate the reaction rate. However, loading active particles via electrostatic interactions (SnS / CoS@NC-CNFs(E)) and physical adsorption (SnS / CoS@NC-CNFs(P)) results in weaker interfacial bonding, leading to lower resistance (R). ct The resistance is relatively high. (Due to...) Figure 29 (b) It can be seen that the slope of the fitted line of SnS / CoS@NC-CNFs(C) material is the smallest, which corresponds to the smallest sodium ion diffusion resistance and the most efficient sodium ion diffusion rate.
[0198] Table 6 lists the σ values for each negative electrode material and their corresponding values. As shown in the table, SnS / CoS@NC-CNFs(C) has the lowest σ value (518.1 Ω s). -0.5 ), It is 1.61 × 10 -17 cm 2 / s, exhibiting optimal sodium ion diffusion kinetics performance.
[0199] Table 6 Fitted values of electrochemical kinetic parameters for SnS / CoS@NC-CNFs
[0200] Figure 30 The images are SEM images of SnS / CoS@NC-CNFs after 200 cycles at 0.1C; (a) and (b) are SEM images of SnS / CoS@NC-CNFs(P) after 200 cycles at different magnifications, (c) is SEM image of SnS / CoS@NC-CNFs(E) after 200 cycles, and (d) is SEM image of SnS / CoS@NC-CNFs(C) after 200 cycles.
[0201] As can be seen from Figures (a)-(b) in Figure 30, after 200 cycles, the SnS / CoS@NC nanoparticles loaded with SnS / CoS@NC exhibit significant agglomeration and detachment, with the carbon framework collapsing and breaking. Figure 30(c) It can be seen that the SnS / CoS@NC nanoparticles supported on SnS / CoS@NC-CNFs(E) exhibit significant aggregation. Figure 30 (d) It can be seen that after 200 charge-discharge cycles, SnS / CoS@NC-CNFs(C) still retains a relatively uniform active particle load, conductive network framework support, and pore structure, without obvious agglomeration, pulverization, or structural collapse, demonstrating its excellent structural integrity and interface stability. Comparative results show that in SnS / CoS@NC-CNFs(C), the covalent bonds (the covalent bonds formed between the aldehyde groups in the aldehyde-modified filter paper and the amino groups of PDA in CoSn(OH)6@PDA) firmly anchor the active material (CoSn(OH)6@PDA) onto the carbon matrix (aldehyde-modified filter paper), fundamentally suppressing drastic structural changes during the charge-discharge process.
[0202] In addition, the morphology of the electrode surface was characterized before cycling and after 200 cycles at 0.1C. Figure 31 The images show SEM images of SnS / CoS@NC-CNFs electrodes before and after cycling. Among them, (a) is the SEM image of SnS / CoS@NC-CNFs(P) electrode before cycling, (b) is the SEM image of SnS / CoS@NC-CNFs(P) electrode after cycling, (c) is the SEM image of SnS / CoS@NC-CNFs(E) electrode before cycling, (d) is the SEM image of SnS / CoS@NC-CNFs(E) electrode after cycling, (e) is the SEM image of SnS / CoS@NC-CNFs(C) electrode before cycling, and (f) is the SEM image of SnS / CoS@NC-CNFs(C) electrode after cycling.
[0203] Depend on Figure 31 (b) As can be seen, obvious cracks appeared on the surface of the SnS / CoS@NC-CNFs(P) electrode after cycling. Figure 31 As can be seen from (c) and (e), the surfaces of the SnS / CoS@NC-CNFs(E) and SnS / CoS@NC-CNFs(C) electrode sheets before cycling are both smooth and dense; Figure 31 As shown in (d) and (f), after 200 cycles, the SnS / CoS@NC-CNFs(C) electrode sheet has a more uniform and flatter surface than the SnS / CoS@NC-CNFs(E), with no obvious cracks.
[0204] 4. Mechanism simulation and analysis of the improvement of sodium storage performance of SnS / CoS Janus heterostructure with NC coating in SnS / CoS@NC (calculation parameters are set according to the inherent properties of SnS and CoS in the Janus structure): (1) Figure 32The diagram shows crystal structure models; where (a) is pure CoS, (b) is pure SnS, and (c) is SnS / CoS. Figure 32 (a) It can be seen that, with blue Co atoms as the core, a three-dimensional crystal framework is constructed with yellow S atoms, exhibiting a typical sulfide layered / network coordination structure. The Co atoms form a stable tetrahedral / octahedral coordination environment with the surrounding S atoms, constituting a complete CoS crystal; Figure 32 (b) It can be seen that the crystal framework, with gray Sn atoms as the core and yellow S atoms forming a Sn-S coordination bond, exhibits the unique layered / chain-like crystal structure of SnS. This structure differs significantly from the framework atomic arrangement of CoS, demonstrating the intrinsic crystal structure of SnS as a single component. Figure 32 (c) It can be seen that the two single-component structures are connected at the interface by S atoms to form a stable heterojunction interface. The structure retains the intrinsic crystal framework of CoS and SnS respectively, and clearly shows the interface atomic arrangement and bonding state of the heterojunction, reflecting the composite structure characteristics of the two materials.
[0205] (2) Figure 33 The diagram shows the crystal structure model of sodium ion adsorption; where (a) is pure CoS, (b) is pure SnS, and (c) is SnS / CoS.
[0206] Depend on Figure 33 (a) It can be seen that a single Na + It is adsorbed onto the surface / defect active sites of CoS crystals, forming adsorption interactions with S atoms in the CoS framework; by Figure 33 (b) It can be seen that a single Na + Adsorbed on the surface active sites of SnS crystals, forming adsorption interactions with S atoms in the SnS framework; by Figure 33 (c) It can be seen that, due to the synergistic effect of CoS and SnS at the interface, Na + It provides more adsorption sites.
[0207] (3) To investigate the interfacial electronic interactions of the NC-coated SnS / CoS Janus heterojunction in SnS / CoS@NC, we calculated its charge difference density. Figure 34 The figures show the calculated charge difference density and the built-in electric field and charge density difference distribution of the SnS / CoS heterojunction; where (a) is the charge difference density diagram of SnS / CoS, and (b) is the pure CoS adsorbed Na... + The charge difference density plots after that, (c) shows pure SnS adsorbed with Na + The charge difference density plot after that, (d) shows the SnS / CoS adsorption of Na +(e) Schematic diagram of the built-in electric field formed by the SnS / CoS heterojunction, and (f) Schematic diagram of the charge density difference distribution of the SnS / CoS heterojunction.
[0208] from Figure 34 (a) It can be seen that after CoS and SnS couple, the Fermi level of CoS shifts to a higher potential, while the Fermi level of SnS shifts to a lower potential. Therefore, the charge redistributes at the CoS and SnS interface, accumulating positive charge (yellow enriched region) and negative charge (cyan enriched region), respectively. This interface charge transfer forms a built-in electric field pointing from CoS to SnS. To further investigate the interaction between different phases and Na... + The interaction between them was analyzed, and the charge difference density of the CoS-Na and SnS-Na systems was calculated respectively. Figure 34 (b) and (c)). In the CoS-Na system ( Figure 34 (b)), Na + Significant charge redistribution exists at the CoS interface, while in the SnS-Na system ( Figure 34 (c)), Na + There is almost no obvious charge difference signal between SnS and SnS, which confirms that pure SnS has a high charge difference. Its adsorption and binding ability is relatively poor. Figure 34 (d) and (e) are the charge difference density diagram and the built-in electric field diagram of the SnS / CoS-Na system, respectively. Due to the electrostatic potential formed by the built-in electric field between CoS and SnS, Na... + Electrons are strongly attracted to the SnS side, while electrons accumulated on the SnS side are neutralized. When the interfacial electric field eventually disappears, the high concentration gradient at the interface will drive Na... + From Fu Na + The SnS side undergoes directional transfer to the CoS side and diffuses rapidly along the heterogeneous interface. Figure 34 The significant change in charge density shown in the charge density difference distribution diagram of the SnS / CoS heterojunction in (f) also indicates that there is a strong electronic interaction between the CoS and SnS heterojunction interfaces, which greatly promotes charge transfer dynamics and fully demonstrates the synergistic optimization effect of the heterostructure.
[0209] In summary, theoretical calculations demonstrate that the construction of SnS / CoS Janus heterostructures can effectively modulate the interfacial electronic structure, significantly enhancing the material's resistance to Na+ through a built-in electric field and cascaded charge transfer. + Adsorption and reactivity.
[0210] (4) In order to quantify the effects of different systems on Na + Adsorption capacity, we through (This formula uses first-principles calculations to evaluate the material's susceptibility to Na.)+ The standard definition of adsorption stability of Na was used to calculate the adsorption stability of Na. + Adsorption energies on pure SnS, pure CoS, and SnS / CoS surfaces; in the above equation, E b Na represents + Adsorption energy (eV) on the substrate material, E total E represents the total energy (eV) of the entire system after adsorption. ad Indicates isolated adsorbent (Na) + Energy (eV), E sub Energy of a pure substrate material (eV); adsorption energy (E) b A negative value indicates that the adsorption process is exothermic and the adsorbed structure is stable. More negative values mean stronger binding interactions, as shown in the following figures. Figure 35 As shown.
[0211] It can be found that Na + The adsorption energy on the pure SnS surface is only -0.29 eV, indicating that the interaction between pure SnS and Na is weak; while Na + The adsorption energy on the pure CoS surface is -1.51 eV, indicating that pure CoS has a high adsorption capacity for Na. + It exhibits stronger adsorption affinity. Notably, the SnS / CoS heterojunction shows stronger adsorption affinity for Na. + The adsorption energy reaches -3.31 eV, significantly lower than that of a single-material system, indicating that the construction of the heterojunction interface greatly enhances the adsorption of Na. + The adsorption effect forms stronger and more stable Na+. + Adsorption sites are identified to optimize the kinetics of sodium storage reactions.
[0212] (5) In order to further explore the effects of different materials on Na + The effect of diffusion kinetics was calculated for Na. + The diffusion energy barriers on pure SnS, pure CoS, and SnS / CoS surfaces are shown in the following results. Figure 36 As shown. It can be observed that Na + The diffusion barrier on a pure SnS surface is as high as 2.19 eV, indicating that Na + Migration resistance is high and diffusion kinetics are poor in pure SnS; however, on the surface of pure CoS, the diffusion barrier drops to 1.76 eV, indicating that the crystal structure of pure CoS is more favorable for Na+. + The migration of Na. It is worth noting that the Na in the SnS / CoS heterojunction... + The diffusion barrier is only 1.04 eV, significantly lower than that of the single-material system, decreasing by approximately 53% compared to SnS and approximately 41% compared to CoS. This indicates that the construction of the SnS / CoS heterojunction interface can reduce the Na₂S diffusion barrier through the built-in electric field and interfacial electronic interactions. +The energy barrier for migration, optimizing Na + The diffusion pathway is improved, thereby significantly enhancing the sodium storage reaction kinetics of the material.
[0213] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode material based on SnS / CoS dual-component metal sulfide, characterized in that, Includes the following steps: (1) CoSn(OH)6 nanocubic precursor was synthesized by coprecipitation method; the molar ratio of Co in the Co source and Sn in the Sn source used to prepare CoSn(OH)6 nanocubic precursor was 7:3~5:5; (2) Heat treatment: The CoSn(OH)6 nano cubic precursor was placed downstream of a tube furnace, and the thiourea was placed upstream of the tube furnace. The mixture was heated under an argon atmosphere and then cooled to room temperature to obtain the anode material based on the SnS / CoS dual-component metal sulfide. In step (2), the temperature is raised to 550℃-650℃ for heat treatment for 3.5-4.5h; the mass ratio of CoSn(OH)6 nano cubic precursor to thiourea is 1:4.5-1:5.5; Step (2) also includes: Step I: Disperse CoSn(OH)6 precursor and dopamine in Tris buffer, sonicate, stir, separate solid and liquid, wash and dry the obtained solid to obtain CoSn(OH)6@PDA; Step I is followed by: Step II: II-1. Immerse filter paper in CoSn(OH)6@PDA dispersion for reaction; the filter paper is aldehyde-modified filter paper and / or polyethyleneimine-modified filter paper; II-2. Remove the filter paper and filter it to obtain the CoSn(OH)6@PDA-filter paper composite material; In step (2), CoSn(OH)6@PDA-filter paper composite material is used instead of CoSn(OH)6@PDA. The resulting anode material based on SnS / CoS dual-component metal sulfide is denoted as SnS / CoS@NC-CNFs.
2. The method for preparing the anode material based on SnS / CoS dual-component metal sulfide as described in claim 1, characterized in that, In step I, dopamine is dispersed in Tris buffer at a concentration of 0.007-0.013 mol / L; The CoSn(OH)6 precursor was dispersed in Tris buffer at a concentration of 1 g / 200 mL. The ultrasonic time is 5-15 minutes, and the stirring time is 22-26 hours.
3. The method for preparing the negative electrode material based on SnS / CoS dual-component metal sulfide as described in claim 1, characterized in that, In step II-1, the reaction temperature is 65℃-75℃, and the reaction time is 3.5h-4.5h; The aldehyde-modified filter paper was prepared by means of the following steps: the filter paper was immersed in a solution containing triethoxysilylbutyraldehyde and reacted at 22℃-28℃ for 10h-14h; the filter paper was removed, washed, and dried to obtain the aldehyde-modified filter paper. Polyethyleneimine-modified filter paper is prepared by a method comprising the following steps: immersing filter paper in a polyethyleneimine assembly solution; soaking at 65℃-75℃ for 3.5h-4.5h, then removing the filter paper, washing, and drying to obtain the polyethyleneimine-modified filter paper; wherein the polyethyleneimine assembly solution contains polyethyleneimine and sodium chloride.
4. The method for preparing the anode material based on SnS / CoS dual-component metal sulfide as described in claim 3, characterized in that, In step II-1, the ratio of filter paper to CoSn(OH)6@PDA dispersion is 1 cm. 2 8mL-1cm 2 12mL; where the amount of filter paper used is expressed in cm. 2 The amount of CoSn(OH)6@PDA dispersion used is calculated in mL; In the CoSn(OH)6@PDA dispersion, the concentration of CoSn(OH)6@PDA is 0.010 g / mL-0.014 g / mL; In a solution containing triethoxysilylbutyraldehyde, the concentration of triethoxysilylbutyraldehyde is 16 g / L-22 g / L; the ratio of filter paper to the solution containing triethoxysilylbutyraldehyde is 3 cm³. 2 8mL-3cm 2 12mL; In the polyethyleneimine assembly solution, the concentration of polyethyleneimine is 1.8 g / L-2.2 g / L, and the concentration of NaCl is 0.18 mol / L-0.22 mol / L; the ratio of filter paper to polyethyleneimine assembly solution is 1 cm³. 2 8mL-1cm 2 12mL.
5. A negative electrode material based on SnS / CoS dual-component metal sulfide, characterized in that, The anode material based on SnS / CoS dual-component metal sulfide is prepared by the method described in any one of claims 1-4.
6. A negative electrode, characterized in that, The negative electrode is the negative electrode material based on SnS / CoS dual-component metal sulfide as described in claim 5.
7. A sodium-ion battery, characterized in that, The sodium-ion battery uses the SnS / CoS dual-component metal sulfide-based negative electrode material as described in claim 5; or, the sodium-ion battery uses the negative electrode as described in claim 6.
Citation Information
Patent Citations
Lithium ion battery negative electrode composite material with tin-cobalt@carbon@trimanganese tetraoxide yolk-shell structure, and preparation method thereof
CN111564613A
Composite sulfide material with three-phase interface heterostructure, preparation method of composite sulfide material and application of composite sulfide material in solid-state battery
CN121938877A